Method for producing solid electrolyte, and solid electrolyte

By mixing the raw materials of lithium, phosphorus and sulfur with solvents, an intermediate solution is formed, and dried using a spray drying device, and setting the spray pressure to 0.01 MPa or above, the problems of insufficient productivity and conductivity of solid electrolytes in the prior art are solved, and the effects of narrow particle size distribution, small median diameter and excellent ionic conductivity are achieved.

CN119563216APending Publication Date: 2025-03-04IDEMITSU KOSAN CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380054090.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-24
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, when manufacturing solid electrolytes, it is difficult to achieve excellent productivity, narrow particle size distribution, small median diameter and excellent ionic conductivity at the same time.

Method used

By mixing the raw material containing lithium atoms, phosphorus atoms and sulfur atoms with a solvent, a solution of intermediate is formed, and dried using a spray drying device, and the spray pressure is set to 0.01 MPa or more to remove the solvent and control the particle size.

Benefits of technology

It realizes solid electrolyte with excellent productivity, narrow particle size distribution, small median diameter and excellent ionic conductivity, and improves battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119563216A_ABST
    Figure CN119563216A_ABST
Patent Text Reader

Abstract

Provided is a method for producing a solid electrolyte having excellent productivity, narrow particle size distribution, small median diameter (D50), and excellent ionic conductivity, and also provided is a method for producing a solid electrolyte having a prescribed median diameter (D50) and particle size distribution. The manufacturing method of the solid electrolyte comprises the following steps: mixing raw material-containing substances containing lithium atoms, phosphorus atoms and sulfur atoms with a solvent to obtain a solution of an intermediate (1); and spraying the solution of the intermediate (1) using a spray drying device, or spraying the solution at a spray pressure of 0.01 MPa or more in the spray drying device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a solid electrolyte and the solid electrolyte. Background Art

[0002] In recent years, with the rapid popularization of information-related devices or communication devices such as personal computers, cameras and mobile phones, the development of batteries used as their power sources has also received attention. In the past, in batteries used for such purposes, electrolytes containing flammable organic solvents were used, but by making the battery fully solid, the safety device is simplified because no flammable organic solvent is used in the battery, and the manufacturing cost and productivity are excellent. Therefore, the development of batteries in which the electrolyte is replaced by a solid electrolyte layer is carried out.

[0003] A bead mill or other pulverizing device is used in the synthesis and particle size control of the solid electrolyte used in the solid electrolyte layer. By using a pulverizer in this way, the manufacturing process is multi-stage and the manufacturing cost is also increased. So far, there has been a possibility of providing a manufacturing method without using a pulverizing device by improving the synthesis process and applying the so-called solution synthesis in a solution to synthesize a solid electrolyte, but a pulverizing device is still needed in the particle size control of the solid electrolyte, and it is expected to improve productivity.

[0004] For solid electrolytes, it is desirable to control the particle size of the solid electrolyte according to its application (the particle size distribution of the solid electrolyte is narrow, the median diameter (D 50 ) small). Solid electrolytes can be used in the positive electrode, negative electrode and solid electrolyte layer of all-solid batteries. In the electrodes (positive electrode, negative electrode), solid electrolytes and electrode active materials (positive electrode active materials, negative electrode active materials) are used in combination. Since both solid electrolytes and electrode active materials are solid electrolytes, if the particle size distribution of the solid electrolyte is narrow, the median diameter (D 50 ), it is easy to form a contact interface between the electrode active material and the solid electrolyte, and the path of ion conduction and electron conduction becomes good. As a result, excellent battery performance can be obtained.

[0005] For example, there is known a method of preparing a raw material such as lithium sulfide in a good solvent solution and spraying the solution into a poor solvent to produce fine particles having a composite of multiple raw material components including lithium and the like and little crystal growth (Patent Document 1).

[0006] In addition, Patent Document 2 discloses a method for manufacturing a solid electrolyte, which includes: supplying a liquid containing a solid electrolyte raw material to a medium that is liquid or gas and has a temperature higher than the boiling point of the solvent, evaporating the solvent, and reacting the solid electrolyte raw material to precipitate an argyrodite-type crystal structure.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2017-18872

[0010] Patent Document 2: Japanese Patent Application Publication No. 2019-169459 Summary of the invention

[0011] Technical problem to be solved by the invention

[0012] The present invention has been made in view of such a situation, and an object of the present invention is to provide a particle size distribution having excellent productivity and a narrow median diameter (D 50 ) small and has excellent ionic conductivity.

[0013] Solutions for solving the above technical problems

[0014] The method for producing a solid electrolyte of the present invention comprises: mixing a raw material containing lithium atoms, phosphorus atoms and sulfur atoms with a solvent to obtain a solution of an intermediate (1); and using a spray drying device and setting the spray pressure of the spray drying device to be above 0.01 MPa to spray the solution of the intermediate (1).

[0015] The method for producing a solid electrolyte of the present invention comprises: mixing a raw material containing lithium atoms, phosphorus atoms and sulfur atoms with a solvent to obtain a solution of an intermediate (1); and spraying the solution of the intermediate (1) using a spray drying device.

[0016] In addition, the solid electrolyte of the present invention is a solid electrolyte having a median diameter (D 50 ) is 1.0 μm or more and less than 9.0 μm, based on the median diameter (D 50 ) and the particle size of 10% of the cumulative volume (D 10 ) and the particle size at which 90% of the cumulative volume is located (D 90 ) particle size distribution ((D 90 -D 10 ) / D 50 ) is less than 2.50.

[0017] Effects of the Invention

[0018] According to the present invention, it is possible to provide a particle having excellent productivity, a narrow particle size distribution, and a median diameter (D 50 ) small and has excellent ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a flowchart for explaining an example of a preferred mode of the production method according to the present embodiment.

[0020] Figure 2The particle size distributions of the solid electrolyte (1) obtained in Example 1, the solid electrolyte (2) obtained in Example 2, and the solid electrolyte (C1) obtained in Comparative Example 1 are shown. DETAILED DESCRIPTION

[0021] Hereinafter, an embodiment of the present invention (hereinafter sometimes referred to as "the present embodiment") is described. In addition, in this specification, the upper and lower limit values ​​involved in the numerical ranges of "above", "below", and "to" are values ​​that can be arbitrarily combined, and the values ​​of the embodiments can also be used as the upper and lower limit values. In addition, preferred provisions can be adopted arbitrarily. That is, a preferred provision can be combined with another preferred provision or multiple provisions. It can be said that the combination of preferred provisions is more preferred.

[0022] (Discovery made by the inventors to complete the present invention)

[0023] The present inventors have conducted intensive studies to solve the above-mentioned technical problems, and as a result, have found the following matters, thereby completing the present invention.

[0024] In the manufacturing method described in the above-mentioned patent document 1, the product is obtained by precipitation in the poor solvent used, so it is necessary to remove the poor solvent and dry it afterwards. In this way, the manufacturing process becomes complicated because it is necessary to remove the poor solvent, etc. In addition, in the process of removing the poor solvent and drying, the particles come into contact with each other, resulting in an increase in particle size, which leads to an increase in the median diameter of the particles.

[0025] In the above-mentioned patent document 2, a manufacturing method for precipitating a solid electrolyte containing a argyrodite-type crystal structure is described as an example. As Example 5, a method for treating a solid electrolyte raw material containing liquid (solvent, pyridine) using a micro-spray drying device is described. However, in the case of using pyridine as a solvent as in the manufacturing method of Example 5, the solid electrolyte is difficult to dissolve in pyridine, so the solid electrolyte raw material containing liquid is a slurry. Therefore, it is different from the method of spraying as a solution as in the manufacturing method of the present embodiment. In the case of spraying as a slurry, if the median diameter of the solid electrolyte contained in the slurry is large, the median diameter of the manufactured solid electrolyte becomes larger, and if the particle size distribution is not narrow, the particle size distribution of the manufactured solid electrolyte is not narrow. The properties of the solid electrolyte manufactured in this way are affected by the properties of the solid electrolyte contained in the slurry.

[0026] In addition, in Reference 2, the spray pressure of the micro-spray drying device is not optimized, and the D of the obtained solid electrolyte is 50 As large as 9μm.

[0027] Furthermore, in the method described in Example 5 of Citation 2, there is room for improvement in terms of productivity, for example, because the spray port is clogged by the solid electrolyte contained in the slurry during spraying.

[0028] As mentioned above, if the particle size distribution of the solid electrolyte is narrow and the median diameter (D 50 ), then the contact interface of electrode active material and solid electrolyte is easily formed, and the path of ion conduction and electronic conduction becomes good. As a result, excellent battery performance can be obtained, but the method described in reference 1 and 2 cannot produce a sufficiently small particle size.

[0029] The present inventors have focused on using an intermediate (1) as a solution, using a spray dryer to dry when removing a solvent from a solution of the intermediate (1), and the spray pressure of the spray dryer. It has been found that when producing a solid electrolyte, by using a solution of the intermediate (1) described later, setting the spray pressure of the spray dryer to 0.01 MPa or more, and drying and removing the solvent contained in the solution of the intermediate (1), or by spraying the solution of the intermediate (1) described later using a spray dryer, and drying and removing the solvent contained in the solution of the intermediate (1), the produced solid electrolyte has a narrow particle size distribution and a median diameter (D 50 ) is small, and thus the ion conductivity is excellent. Based on such a view, the inventors of the present invention have completed the following structure of the manufacturing method of the present embodiment. The manufacturing method of the present invention controls the particle size of the solid electrolyte (set to a narrow particle size distribution, a median diameter (D 50 ) is small), and the solvent removal based on drying can also be performed simultaneously, so it can be said that the productivity is excellent. In addition, regarding the solid electrolyte of the present invention, there is no particular limitation on the manufacturing method thereof, for example, it can be easily manufactured by the manufacturing method of the present invention described above, and the particle size distribution is narrow, and the median diameter (D 50 )Small.

[0030] (Various Aspects of the Present Embodiment)

[0031] Hereinafter, methods for producing solid electrolytes according to first to thirteenth aspects and solid electrolytes according to fourteenth to sixteenth aspects of the present embodiment will be described.

[0032] A method for producing a solid electrolyte according to a first aspect of the present embodiment is as follows:

[0033] A method for manufacturing a solid electrolyte, comprising:

[0034] Mixing a raw material containing lithium atoms, phosphorus atoms and sulfur atoms with a solvent to obtain a solution of an intermediate (1); and

[0035] The solution of the intermediate (1) is sprayed using a spray dryer at a spray pressure of 0.01 MPa or more.

[0036] Figure 1 A flow chart of a preferred embodiment of the method for manufacturing a solid electrolyte of the present embodiment is shown in FIG. The method for manufacturing the present embodiment uses a spray drying device to spray a solution of the intermediate (1) to remove the solvent from the solution of the intermediate (1), thereby being able to simultaneously remove the solvent and control the particle size of the solid electrolyte, and thus can be said to be a production method with excellent productivity.

[0037] In addition, the particle size distribution of the obtained solid electrolyte is narrow, and the median diameter (D 50 ) is small, therefore as mentioned above, easily forms the contact interface of electrode active material and solid electrolyte, and the path of ion conduction and electronic conduction becomes good. In addition, due to the excellent ion conductivity of the obtained solid electrolyte, therefore can obtain excellent battery performance by using it.

[0038] The solution of the intermediate (1) is obtained by mixing the raw material content described later and the solvent described later. If the intermediate (1) is not a solution, when the solution is sprayed using a spray drying device and the solvent is dried, the particle size of the sprayed droplets cannot be reduced even if the spray pressure is adjusted. If the particle size of the droplets is large, the particle size of the manufactured solid electrolyte will also become larger. In this way, if it is not a solution, the particle size of the droplets cannot be reduced, and especially if it is a slurry, the manufactured particle size is affected by the particle size of the solid contained in the slurry. "The particle size is affected" means that when spraying as a slurry as described above, if the median diameter of the solid electrolyte contained in the slurry is large, the median diameter of the manufactured solid electrolyte becomes larger, and if the particle size distribution is not narrow, the particle size distribution of the manufactured solid electrolyte is not narrow.

[0039] In this specification, "solution" not only means a solution in which a solute is completely dissolved in a solvent to form a uniform state, but also includes the concept of a solution in which an incompletely dissolved solute is less than 10% by mass of the total amount of the raw material. The content of the incompletely dissolved solute is preferably less than 5% by mass of the total amount of the raw material, more preferably less than 3% by mass. In addition, the incompletely dissolved solute can also become a colloid. In addition, an amorphous solid electrolyte or a crystalline solid electrolyte can also be included in the solution as a secondary component.

[0040] In this specification, "dissolving" means preparing the above-mentioned solution using a solute and a solvent.

[0041] In this specification, "slurry" refers to a mixture of a solid substance and a solvent, and is a fluid having a certain fluidity due to the presence of a solvent, and does not include the above-mentioned solution.

[0042] In this specification, the term "solid electrolyte" refers to an electrolyte that remains solid at 25° C. in a nitrogen atmosphere, and is a solid electrolyte that contains lithium atoms, sulfur atoms, phosphorus atoms, and, if necessary, halogen atoms, and has ion conductivity due to lithium atoms.

[0043] In this specification, the "raw material-containing substance" includes raw materials for producing a solid electrolyte, and is a single substance or a mixture of compounds containing lithium atoms, phosphorus atoms, and sulfur atoms.

[0044] In this specification, "the particle size is controlled" means that the particle size distribution is narrow as described above, and the median diameter (D 50 ) is small. After the raw material content is mixed with a solvent to obtain a solution of the intermediate (1), the solvent is dried using a spray drying device at a specific spray pressure, thereby producing a solid electrolyte with controlled particle size and excellent ion conductivity. By passing through the solution of the intermediate (1), the particle size of the solid electrolyte can be easily controlled, and a solid electrolyte with excellent ion conductivity can be produced.

[0045] The median diameter of the solid electrolyte (D 50 ) can be measured or calculated by the method described in the embodiments, for example. Figure 2 The particle size distribution shown in FIG. 1 can confirm the particle size distribution of the solid electrolyte. 10 ) and the particle size of 90% of the cumulative volume (D 90 ) is also the same.

[0046] A method for producing a solid electrolyte according to a second aspect of the present embodiment is, in the above-mentioned first aspect,

[0047] The spray pressure is 0.05 MPa or more.

[0048] The particle size of the manufactured solid electrolyte can be adjusted by the spray pressure of the spray drying device. By increasing the spray pressure, the particle size of the sprayed droplets can be reduced, and by reducing the particle size of the droplets, the particle size of the manufactured solid electrolyte can be reduced. If the spray pressure is 0.05MPa or more, the particle size of the sprayed droplets can be reduced, and the particle size of the manufactured solid electrolyte can be controlled, so it is preferred.

[0049] A method for producing a solid electrolyte according to a third aspect of the present embodiment is as follows:

[0050] A method for manufacturing a solid electrolyte, comprising:

[0051] Mixing a raw material containing lithium atoms, phosphorus atoms and sulfur atoms with a solvent to obtain a solution of an intermediate (1); and

[0052] The solution of the intermediate (1) is sprayed using a spray drying apparatus.

[0053] As described above, by spraying the solution of the intermediate (1) using a spray drying device, the solvent contained in the solution of the intermediate (1) is dried and removed. That is, only by spraying the solution of the intermediate (1) using a spray drying device, the particle size distribution of the produced solid electrolyte is narrowed, and the median diameter (D 50 ) is small, and thus the ionic conductivity is excellent.

[0054] Regarding the differentiated use of the above-mentioned first and third schemes, for example, when it is necessary to set the desired particle size, the manufacturing method of the first scheme can be adopted to adjust the spray pressure to a specified range through the first scheme. When there is no such requirement, the manufacturing method of the third scheme can be adopted in which only spraying is sufficient.

[0055] A fourth method for producing a solid electrolyte according to the present embodiment is, in any one of the first to third methods described above,

[0056] The median diameter (D 50 ) is less than 9.0μm.

[0057] If the D 50 If the particle size distribution is less than 9.0 μm, the median diameter (D 50 ) is a small solid electrolyte, so it is easy to form a contact interface between the electrode active material and the solid electrolyte, the pathways for ion conduction and electron conduction become good, and excellent battery performance can be obtained, so it is preferred.

[0058] A fifth method for producing a solid electrolyte according to the present embodiment is, in any one of the first to fourth methods,

[0059] The temperature of the intermediate (1) at the spray outlet of the spray drying device is 350°C or less.

[0060] If the temperature of the intermediate (1) at the spray outlet of the spray drying device is 350°C or less, the particle size of the sprayed droplets becomes smaller and the particle size distribution of the droplets also becomes smaller, so that the particle size of the produced solid electrolyte can be controlled, which is preferred.

[0061] In this way, the particle size and particle size distribution of the manufactured solid electrolyte vary greatly depending on the particle size and particle size distribution of the sprayed droplets. The particle size and particle size distribution of the sprayed droplets can be controlled by the spray pressure, so setting the spray pressure to a specific range becomes crucial in the manufacture of solid electrolytes.

[0062] A sixth method for producing a solid electrolyte according to the present embodiment is, in any one of the first to fifth methods,

[0063] No further pulverization of the solid electrolyte was performed.

[0064] The solid electrolyte produced in any one of the first to fifth embodiments is a solid electrolyte with controlled particle size. Therefore, the step of further pulverizing to reduce the particle size can be omitted, and in order to improve productivity, the solid electrolyte can be used as a solid electrolyte for batteries, etc. without further pulverizing. Therefore, in order to simplify the manufacturing process and improve productivity, it is preferred that after spraying the solution of the intermediate (1) using a spray drying device, no further pulverization operation is performed.

[0065] A seventh method for producing a solid electrolyte according to the present embodiment is, in any one of the first to sixth methods,

[0066] The raw material-containing substance further contains a halogen atom.

[0067] It is preferred that the raw material-containing substance further contains halogen atoms because the solid electrolyte contains a crystal form with high ion conductivity.

[0068] An eighth aspect of the present embodiment is a method for producing a solid electrolyte, in any one of the first to seventh aspects,

[0069] The solvent includes at least one selected from a complexing agent and a solvent in which the raw material-containing substance can be dissolved.

[0070] As described later, by making the solvent contain at least one selected from the complexing agent and the raw material-containing solvent, a solution of the intermediate (1) can be prepared. When the solution of the intermediate (1) is sprayed using a spray drying device, the particle size of the sprayed droplets can be reduced, thereby controlling the particle size of the solid electrolyte produced and improving productivity, which is preferred.

[0071] In order to include at least one of a complexing agent and a solvent for solubilizing the raw material contents as a solvent, in addition to the case of using a solvent containing a complexing agent and a solvent for solubilizing the raw material contents, it also includes a scheme of using a solvent containing a complexing agent after using a solvent containing a solvent for solubilizing the raw material contents, and conversely, a scheme of using a solvent containing a complexing agent after using a solvent containing a solvent for solubilizing the raw material contents.

[0072] A method for producing a solid electrolyte according to a ninth aspect of the present embodiment is, in the eighth aspect described above,

[0073] The solvent includes a solvent in which the raw material-containing substances can be dissolved.

[0074] In the present specification, "solubilize" means that the solvent can dissolve the solute, and the "raw material content solubilizing solvent" described below is a solvent that can dissolve the raw material content, and is a solvent that can prepare the solution by mixing with the raw material content.

[0075] It is preferred that the solvent contain a solvent that dissolves the raw material content, because a solution of the intermediate (1) can be easily obtained, the particle size of the produced solid electrolyte can be controlled, and productivity can be improved.

[0076] A method for producing a solid electrolyte according to a tenth aspect of the present embodiment is, in the eighth or ninth aspect described above,

[0077] The solvent contains a complexing agent.

[0078] The complexing agent described later forms a complex with the raw material containing material. By forming a complex, the raw material containing material solubilizing solvent used as needed is difficult to directly contact with the raw material containing material, so the reaction between the raw material containing material solubilizing solvent and the raw material containing material is suppressed, so it is preferred. In addition, when the raw material containing material contains halogen atoms, a solid electrolyte in which the halogen atoms are more dispersed and fixed can be obtained, so it is preferred. Furthermore, by using the spray of a spray drying device, a uniform powder can be obtained, so a solid electrolyte with high ionic conductivity can be obtained, and the result is that high ionic conductivity is easily obtained, so it is preferred.

[0079] Furthermore, the use of a complexing agent is preferred because a solid electrolyte can be produced by mixing without having to set the temperature to a high temperature.

[0080] The method for producing a solid electrolyte according to an eleventh aspect of the present embodiment is, in any one of the eighth to tenth aspects,

[0081] The solvent in which the raw material-containing substance can be dissolved includes an alcohol solvent.

[0082] It is preferred that the solvent for making the raw material-containing substance soluble include an alcohol solvent because it facilitates preparation of a solution of the intermediate (1).

[0083] A method for producing a solid electrolyte according to a twelfth aspect of the present embodiment is, in any one of the eighth to eleventh aspects,

[0084] The solvent further comprises a non-polar solvent.

[0085] It is preferred that the solvent further contains a nonpolar solvent described below because the amount of the complexing agent or the solvent that dissolves the raw material content used can be reduced as necessary.

[0086] A thirteenth aspect of the present embodiment is a method for producing a solid electrolyte, in any one of the eighth to twelfth aspects,

[0087] After the raw material-containing substance and the solvent containing the complexing agent are mixed, a solvent containing a solvent in which the raw material-containing substance can be dissolved is further added and mixed.

[0088] After the raw material containing substance is mixed with the solvent containing the complexing agent to form a complex, a solvent containing the raw material containing substance solubilizing solvent is added and mixed, thereby obtaining a higher effect via the complex, so it is preferred. The effect via the complex is described later, and by forming a complex from a solid electrolyte (especially Li3PS4), the raw material containing substance solubilizing solvent and the raw material containing substance are difficult to directly contact, so the reaction between the raw material containing substance solubilizing solvent and the raw material containing substance is suppressed, so it is preferred.

[0089] The solid electrolyte of the fourteenth aspect of the present embodiment is,

[0090] A solid electrolyte, the median diameter (D 50 ) is 1.0 μm or more and less than 9.0 μm, based on the median diameter (D 50 ) and the particle size of 10% of the cumulative volume (D 10 ) and the particle size at which 90% of the cumulative volume is located (D 90 ) particle size distribution ((D 90 -D 10 ) / D 50 ) is less than 2.50.

[0091] The method for manufacturing the solid electrolyte of the present embodiment is not particularly limited, and it can be easily manufactured by, for example, the method for manufacturing the solid electrolyte of the present embodiment described above, and the particle size of the obtained solid electrolyte can be adjusted, for example, by adjusting the spray pressure as described above. The solid electrolyte of the present embodiment is a solid electrolyte having a predetermined median diameter and particle size distribution obtained by, for example, adjusting the spray pressure, among the solid electrolytes obtained by the method for manufacturing the solid electrolyte of the present embodiment described above. The median diameter (D 50 ) is 1.0 μm or more and less than 9.0 μm, the median diameter is extremely small and the particle size distribution ((D 90 -D 10 ) / D 50 ) is extremely narrow and is below 2.50.

[0092] As described above, the solid electrolyte of this embodiment has a small median diameter within a predetermined range and a narrow particle size distribution, so it can be densely packed when manufactured into a battery, and the resistance can be reduced by reducing the interface contact. As a result, excellent battery performance is achieved.

[0093] The solid electrolyte of the fifteenth aspect of the present embodiment is, in the fourteenth aspect,

[0094] The specific surface area is 15cm 2 / g or above.

[0095] If the solid electrolyte has a higher specific surface area of ​​15 cm 2 When the specific surface area is 200 nm or more, the battery can be densely packed when it is manufactured, so that excellent battery performance can be easily obtained.

[0096] A solid electrolyte according to a sixteenth aspect of the present embodiment is, in the fourteenth or fifteenth aspect,

[0097] It has a argyrodite-type crystal structure.

[0098] It is known that a solid electrolyte having an argyrodite-type crystal structure has high ion conductivity. By making the solid electrolyte itself have a crystal structure exhibiting high ion conductivity, the battery performance can be further improved.

[0099] Hereinafter, the method for producing the solid electrolyte according to the present embodiment will be described in more detail corresponding to the above-described embodiment.

[0100] [Method for producing solid electrolyte]

[0101] The method for producing a solid electrolyte of the present embodiment is a method for producing a solid electrolyte, comprising: mixing a raw material containing a lithium atom, a phosphorus atom, and a sulfur atom with a solvent to obtain a solution of an intermediate (1); and using a spray drying device and setting the spray pressure of the spray drying device to 0.01 MPa or more to spray the solution of the intermediate (1). In addition, another method for producing a solid electrolyte of the present embodiment is a method for producing a solid electrolyte, comprising: mixing a raw material containing a lithium atom, a phosphorus atom, and a sulfur atom with a solvent to obtain a solution of an intermediate (1); and using a spray drying device to spray the solution of the intermediate (1).

[0102] Hereinafter, after explaining the production method, the raw material content, the intermediate (1), the solid electrolyte, the solvent, and the like will be explained in detail.

[0103] <Obtaining a Solution of Intermediate (1)>

[0104] The method for producing a solid electrolyte according to the present embodiment needs to include mixing the raw material-containing substance described later with the solvent described later to obtain a solution of the intermediate (1) described later.

[0105] Regarding the method of mixing the raw material-containing substance described later with the solvent described later to obtain the solution of the intermediate (1) described later, there is no particular limitation as long as the solution of the intermediate (1) described later can be obtained, and various methods can be exemplified depending on the solvent used and the order of adding the solvent.50 ) and excellent in ionic conductivity, preferably the following (I) to (V), more preferably (I) to (III), in order to fully reflect the complex formation effect, it is further preferred that after the raw material content is mixed with a solvent containing a complexing agent, a solvent containing a solubilizing solvent for the raw material content is further added and mixed, and since the use of a complexing agent and / or a solubilizing solvent for the raw material content can reduce their usage, (II) is further preferred.

[0106] (I) The raw material-containing substance and the complexing agent are mixed (to obtain a slurry containing a complex), and a solvent that can dissolve the raw material-containing substance is further added and mixed to prepare a solution of the intermediate (1).

[0107] (II) The raw material-containing substance, the nonpolar solvent and the complexing agent are mixed (to obtain a slurry containing a complex), and a solvent that can dissolve the raw material-containing substance is further added and mixed to prepare a solution of the intermediate (1).

[0108] (III) The raw material-containing substance, a solvent in which the raw material-containing substance can be dissolved, and a complexing agent are mixed to prepare a solution of the intermediate (1).

[0109] (IV) The raw material-containing substance, a solvent in which the raw material-containing substance can be dissolved, a non-polar solvent and a complexing agent are mixed to prepare a solution of the intermediate (1).

[0110] (V) The raw material-containing substance, a solvent in which the raw material-containing substance can be dissolved, and a non-polar solvent are mixed to prepare a solution of the intermediate (1).

[0111] <Mixed>

[0112] The mixing in the method for producing the solid electrolyte of the present embodiment is not particularly limited as long as the raw material content described later can be mixed with the solvent described later to obtain a solution of the intermediate (1) described later. The raw material content can be dissolved in the solvent for mixing, or the raw material content can be mixed without completely dissolving it through a suspension in which a solid and a liquid coexist. As long as a solution is obtained after mixing, for example, a slurry can be used in the intermediate stage as in (I) and (II) above.

[0113] The mixing may be performed by mixing the raw material content described later with a solvent including a solvent in which the raw material content described later is soluble, or by mixing the raw material content described later with a solvent including a complexing agent described later.

[0114] The use of a solvent in which the raw material-containing substance can be dissolved is preferred because a solution of the intermediate (1) can be easily obtained.

[0115] In addition, by using a complexing agent, a solid electrolyte can be manufactured by mixing without setting a high temperature, and a complex is formed by using a complexing agent, so that the raw material containing material solubilizing solvent used as needed is difficult to directly contact with the raw material containing material, so that the reaction between the raw material containing material solubilizing solvent and the raw material containing material can be suppressed, etc., and thus it is preferred. In addition, when the raw material containing material contains halogen atoms, a solid electrolyte in which the halogen atoms are more dispersed and fixed can be obtained, so it is preferred.

[0116] From the viewpoint of preventing granulation in which the particle size increases during the mixing process and being able to produce at low temperature using a simple device, it is preferably carried out in a solvent as in the uniform method and the heterogeneous method. From the viewpoint of achieving high ion conductivity and reducing the environmental load associated with the use of a solvent, the solid phase method is preferred.

[0117] The raw material contents may be solid or liquid, and are usually solid.

[0118] The intermediate (1) is mixed with a solvent to form a solution. However, if the intermediate (1) is not a solution, the particle size of the solid electrolyte produced by the production method of the present embodiment cannot be controlled as described above.

[0119] The mixing method is not particularly limited, and the raw material content and the solvent, which are separately prepared, may be charged into an apparatus capable of mixing the raw material content and the solvent and mixed.

[0120] The mixing of the present embodiment may include stirring and crushing, preferably using a stirrer, a mixer or a crusher, more preferably using a stirrer and a mixer. In the case of obtaining a solution of the intermediate (1), a stirrer is further preferably used. In the case of obtaining the intermediate (1) in the form of a slurry and then making a solution, the particle size of the solid component contained in the slurry affects the particle size of the solid electrolyte manufactured in the present embodiment, so a crusher is further preferably used in the manufacturing process of the intermediate (1).

[0121] As agitators and mixers, for example, a mechanical stirring mixer having stirring blades in a tank can be exemplified. The mechanical stirring mixer can exemplify a high-speed stirring mixer, a double-arm mixer, etc., and from the viewpoint of improving the uniformity of the raw materials in the mixture of the raw material containing material and the complexing agent and obtaining higher ion conductivity, it is preferred to use a high-speed stirring mixer. In addition, as a high-speed stirring mixer, a vertical axis rotating mixer, a horizontal axis rotating mixer, etc. can be exemplified, and any type of mixer can also be used.

[0122] The shape of the stirring blade used in the mechanical stirring mixer may be a blade type, an arm type, an anchor type, a paddle type, a stirring paddle type, a belt type, a multi-stage blade type, a double-arm type, a bucket type, a double-shaft blade type, a flat blade type, a C-type blade type, etc. From the viewpoint of improving the uniformity of the raw materials contained in the raw material and obtaining higher ion conductivity, it is preferred to use a bucket type, a flat blade type, a C-type blade type, etc.

[0123] In addition, when a small amount is produced, stirring with a stirring bar may be used.

[0124] The temperature conditions for mixing the raw material content and the solvent are not particularly limited, and are, for example, -30 to 100°C, preferably -10 to 50°C, and more preferably about room temperature (23°C) (for example, about room temperature ±5°C). In addition, the mixing time is about 0.1 to 150 hours, and from the viewpoint of more uniform mixing and obtaining higher ion conductivity, it is preferably 0.2 to 120 hours, more preferably 0.3 to 100 hours, and further preferably 0.5 to 80 hours.

[0125] The pulverizer may, for example, be a pulverizer having a rotating body capable of stirring the solid electrolyte.

[0126] By adjusting the peripheral speed of the rotating body of the pulverizer, the crushing (microparticulation) and granulation (grain growth) of the solid electrolyte can be adjusted. That is, in addition to mixing, the median diameter can be reduced by crushing, or the median diameter can be increased by granulation, so the morphology of the solid electrolyte can be easily and freely adjusted. More specifically, by rotating the rotating body at a low peripheral speed, crushing can be performed, and by rotating the rotating body at a high peripheral speed, granulation can be performed. In this way, the morphology of the solid electrolyte can be easily adjusted only by adjusting the peripheral speed of the rotating body.

[0127] Regarding the peripheral speed of the rotating body, the low peripheral speed and the high peripheral speed can vary according to the particle size, material, usage amount, etc. of the medium used in the pulverizer, for example, and therefore cannot be stipulated in general. For example, in the case of a device that does not use a pulverizing medium such as a high-speed rotating film-type mixer, even at a relatively high peripheral speed, crushing mainly occurs and it is difficult to cause granulation. On the other hand, in the case of a device that uses a pulverizing medium such as a ball mill or a bead mill, as described above, crushing can be performed at a low peripheral speed, and granulation can be performed at a high peripheral speed. Therefore, if the prescribed conditions of the pulverizing device, the pulverizing medium, etc. are the same, the peripheral speed at which crushing can be performed is smaller than the peripheral speed at which granulation can be performed. Therefore, for example, in the condition that granulation can be performed with a peripheral speed of 6 m / s as the boundary, a low peripheral speed refers to less than 6 m / s, and a high peripheral speed refers to more than 6 m / s.

[0128] In addition, as a pulverizer, as a more specific device, for example, a media type pulverizer can be mentioned. The media type pulverizer is roughly divided into a container driven type pulverizer and a media stirring type pulverizer.

[0129] Examples of container-driven pulverizers include stirring tanks, pulverizing tanks, or ball mills and beads mills in combination thereof. As ball mills and beads mills, various types such as rotary, rolling, vibrating, and planetary types can be used.

[0130] In addition, as media stirring type pulverizers, there can be cited: impact pulverizers such as cutter mills, hammer mills, and pin mills; tower type pulverizers such as tower mills; stirring trough type pulverizers such as attritors, wet sand mills (aquamizers), and sand mills; flow trough type pulverizers such as viscose mills and coarse crushers; flow tube type pulverizers; ring type pulverizers such as combined ball mills; continuous dynamic type pulverizers; and other various pulverizers.

[0131] In the mechanical treatment of the solid electrolyte, when the intermediate (1) is used as a slurry, from the viewpoint of being easier to adjust the desired form, a container-driven pulverizer is preferred, wherein a bead mill or a ball mill is preferred. In a container-driven pulverizer such as a bead mill or a ball mill, a rotating body capable of stirring a precursor for mechanical treatment is provided with a container such as a stirring tank or a pulverizing tank for accommodating the precursor for mechanical treatment. Therefore, as described above, the form of the solid electrolyte can be easily adjusted by adjusting the peripheral speed of the rotating body.

[0132] For bead mills and ball mills, the shape can be adjusted by adjusting the particle size, material, and amount of beads, balls, etc. used, so more detailed shape adjustment can be performed, and shapes that have not been available before can also be adjusted. For example, as a bead mill, a centrifugal separation type that can use extremely fine particles (about φ0.015 to 1 mm), that is, a so-called microbead type (such as Ultra Apex Mill (UAM) etc.) can also be used.

[0133] Regarding the adjustment of the morphology, there is the following tendency: the smaller the energy imparted to the solid electrolyte, that is, the lower the circumferential speed of the rotating body or the smaller the particle size of beads, balls, etc., the smaller the median diameter becomes (crushing) and the larger the specific surface area becomes. On the other hand, the larger the energy, that is, the higher the circumferential speed of the rotating body or the larger the particle size of beads, balls, etc., the larger the median diameter becomes (granulation) and the smaller the specific surface area becomes.

[0134] Furthermore, for example, there is a tendency that the median diameter becomes larger (granulation) as the mechanical treatment time becomes longer.

[0135] The particle size of the media used in the bead mill, ball mill, etc. can be appropriately determined in consideration of the desired form and the type and scale of the device used, but is usually preferably 0.01 mm or more, more preferably 0.015 mm or more, further preferably 0.02 mm or more, and further preferably 0.04 mm or more, and the upper limit is preferably 3 mm or less, more preferably 2 mm or less, further preferably 1 mm or less, and further preferably 0.8 mm or less.

[0136] In addition, examples of the material of the medium include metals such as stainless steel, chrome steel, and tungsten carbide; ceramics such as zirconium oxide and silicon nitride; and minerals such as agate.

[0137] The processing time of the mechanical treatment can be appropriately determined in consideration of the desired form and the type and scale of the device used. It is usually preferably 5 seconds or more, more preferably 30 seconds or more, further preferably 3 minutes or more, and further preferably 15 minutes or more. The upper limit is preferably 5 hours or less, more preferably 3 hours or less, further preferably 2 hours or less, and further preferably 1.5 hours or less.

[0138] The peripheral speed of the rotating body in the mechanical treatment (the rotational speed in the devices such as bead mills and ball mills) is appropriately determined by considering the desired form and the type, scale, etc. of the device used, and is usually preferably more than 0.5m / s, more preferably more than 1m / s, more preferably more than 2m / s, more preferably more than 3m / s, and as the upper limit, it is preferably below 55m / s, more preferably below 40m / s, more preferably below 25m / s, and more preferably below 15m / s. In addition, the peripheral speed can be the same or can be changed midway.

[0139] <Drying using a spray dryer>

[0140] The method for producing the solid electrolyte of the present embodiment requires the following operations: using a spray dryer and setting the spray pressure of the spray dryer to 0.01 MPa or more to spray the solution of the intermediate (1), or using a spray dryer to spray the solution of the intermediate (1).

[0141] By spraying the solution of the intermediate (1), the solvent can be removed from the solution of the intermediate (1) by drying. In addition, if the spray pressure of the spray dryer is less than 0.01 MPa, the particle size of the droplets sprayed from the spray dryer becomes larger, showing a tendency that it is difficult to control the particle size of the solid electrolyte manufactured by the manufacturing method of the present embodiment. By adjusting the spray pressure in this way, the particle size of the droplets can be controlled, and the particle size of the manufactured solid electrolyte can be controlled. On the other hand, as described above, by spraying the solution of the intermediate (1) only using a spray dryer, the particle size of the droplets can be fully controlled regardless of the spray pressure, so that a solid electrolyte with a narrow particle size distribution and a small median diameter can be obtained. Therefore, for example, in the case of a solid electrolyte having a desired particle size, a method of adjusting the spray pressure of the spray dryer within a range of 0.01 MPa or more can be used. In the case where it is not required, a method of spraying the solution of the intermediate (1) using only a spray dryer can be used.

[0142] In order to control the particle size of the solid electrolyte, the spray pressure of the spray drying device is preferably 0.02 MPa or more, more preferably 0.03 MPa or more, further preferably 0.05 MPa or more, further preferably 0.12 MPa or more, more particularly preferably 0.18 MPa or more, and further particularly preferably 0.25 MPa or more.

[0143] The upper limit is not particularly limited and is determined according to the performance and specifications of the device, but is usually 20.00 MPa or less.

[0144] In the embodiment in which the solution of the intermediate (1) is sprayed independently of the spray pressure, the spray pressure is preferably within the above range including 0.01 MPa or more from the viewpoint of easier control of the particle size.

[0145] As described above, by setting the spray pressure to a specific range, the flow rate of the solution of the intermediate (1) in the nozzle can be set to a certain level or above, and good dispersibility can be easily obtained, so that a solid electrolyte with a small particle size can be easily obtained without agglomeration. The sprayed droplets are dried and removed by removing the solvent contained in the solution of the intermediate (1), thereby obtaining a dry powder. The dry powder is a solid electrolyte or a complex, and is subjected to heating and / or pulverization as described below as needed, thereby becoming a solid electrolyte manufactured by the manufacturing method of this embodiment. When the median diameter (D 50 ) so that the median diameter (D 50 ) determines the spray pressure in a manner that becomes the target value.

[0146] The spray drying apparatus used in the production method of the present embodiment may be an apparatus in which the solution of the intermediate (1) is sprayed together with a heated gas from a spray nozzle apparatus and, if necessary, is brought into contact with another heated gas to be dried.

[0147] Regarding the conditions for use when using a spray drying apparatus, they can be appropriately determined according to the type of solvent contained in the solution of the intermediate (1). Since it varies depending on the boiling point of the solvent, etc., it is impossible to stipulate in general terms. However, when the temperature of the solution of the intermediate (1) at the spray outlet of the spray drying apparatus is below 350°C, the solvent dries from the sprayed droplets at an appropriate rate and the particle size of the solid electrolyte is controlled. Therefore, it is preferably below 300°C, more preferably below 250°C, and even more preferably below 230°C.

[0148] The lower limit is preferably 80° C. or higher, more preferably 100° C. or higher, in order to shorten the drying time and improve productivity.

[0149] When the solvent contains a complexing agent and the intermediate (1) contains a complex, the temperature is more preferably 150° C. or higher, and even more preferably 180° C. or higher, in order to remove the complexing agent from the complex.

[0150] When the crystalline solid electrolyte described below is obtained by spraying the solution of the intermediate (1) using a spray dryer, the temperature is more preferably 150° C. or higher, and further preferably 180° C. or higher for crystallization.

[0151] In addition, the supply amount of the solution of the intermediate (1) to the nozzle can be changed according to the scale of the spray drying device, so it cannot be set uniformly, and can be appropriately determined according to the scale. It is usually set to about 1 to 60 g / minute. From the viewpoint of drying in a shorter time, it is preferably 3 to 50 g / minute, more preferably 5 to 40 g / minute, and even more preferably 10 to 30 g / minute.

[0152] The operating conditions of the spray drying apparatus can be implemented by the method described in Examples, for example.

[0153] The fluid containing the gas supplied as the heat medium and the powder of the solid electrolyte etc. which has passed through the spray drying device can be supplied to the bag filter and recovered. As the bag filter, the bag filter described as the bag filter which can be used in the above fluidized drying can be used.

[0154] As the filter used for the bag filter, there are no particular restrictions on the use of filters, and examples include filters made of raw materials such as polypropylene, nylon, acrylic acid, polyester, kapok, wool, heat-resistant nylon, polyamide-polyimide, PPS (polyphenylene sulfide), glass fiber, PTFE (polytetrafluoroethylene), etc. In addition, a functional filter such as an electrostatic filter can also be used. Among them, preferably, a filter made of heat-resistant nylon, polyamide-polyimide, PPS (polyphenylene sulfide), glass fiber, PTFE (polytetrafluoroethylene) is used, more preferably, a filter made of heat-resistant nylon, PPS (polyphenylene sulfide), PTFE (polytetrafluoroethylene) is used, and a filter made of PTFE (polytetrafluoroethylene) is particularly preferred.

[0155] <Ingredients in Raw Materials>

[0156] The raw material content used in this embodiment needs to contain lithium atoms, phosphorus atoms, and sulfur atoms. By making the raw material content contain lithium atoms, phosphorus atoms, and sulfur atoms, a solid electrolyte containing these atoms can be produced.

[0157] The above-mentioned raw material content includes one or more raw materials for manufacturing solid electrolytes. The raw material content may be a monomer of a raw material containing lithium atoms, phosphorus atoms and sulfur atoms, or may be a mixture. In addition, the raw material content and the raw material may further contain halogen atoms. That is, the raw material content may contain a raw material (compound) containing halogen atoms as needed.

[0158] As the raw material contained in the raw material content, for example, a compound containing at least one of a lithium atom, a sulfur atom and a phosphorus atom can be used, and a halogen atom can also be contained as needed. More specifically, examples include: lithium sulfide; phosphorus sulfide such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); solid electrolytes such as amorphous Li3PS4 or crystalline Li3PS4 having a PS4 structure as a molecular structure obtained from lithium sulfide and phosphorus sulfide. As compounds containing halogen atoms, there can be mentioned: lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; phosphorus halides such as various phosphorus fluorides (PF3, PF5), various phosphorus chlorides (PCl3, PCl5, P2Cl4), various phosphorus bromides (PBr3, PBr5), and various phosphorus iodides (PI3, P2I4); thiophosphoryl halides such as thiophosphoryl fluoride (PSF3), thiophosphoryl chloride (PSCl3), thiophosphoryl bromide (PSBr3), thiophosphoryl iodide (PSI3), thiophosphoryl fluoride dichloride (PSCl2F), and thiophosphoryl fluoride dibromide (PSBr2F); and raw materials composed of at least two atoms selected from the above four atoms, halogen monomers such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2), preferably chlorine (Cl2), bromine (Br2), and iodine (I2), and more preferably bromine (Br2) and iodine (I2).

[0159] As the raw material content, lithium sulfide and phosphorus sulfide are preferred. When a raw material containing a halogen atom is used, it is more preferred that at least one selected from lithium halide, phosphorus halide and halogen molecule is contained.

[0160] By using at least one selected from lithium sulfide, phosphorus sulfide, lithium halide, phosphorus halide and halogen molecules, a solid electrolyte with high ionic conductivity can be obtained, so it is preferred. If lithium halide is used together with the complexing agent described later in the introduction of halogen atoms in the solid electrolyte, separation of halogen atoms does not occur in the process of removing the solvent described later, and a solid electrolyte with high ionic conductivity can be obtained, so it is preferred.

[0161] Substances that can be used as raw materials other than the above-mentioned ones include, for example, raw materials containing at least one atom selected from the above-mentioned four atoms and atoms other than the four atoms. More specifically, they include: lithium compounds such as lithium oxide, lithium hydroxide, and lithium carbonate; alkali metal sulfides such as sodium sulfide, potassium sulfide, rubidium sulfide, and cesium sulfide; metal sulfides such as silicon sulfide, germanium sulfide, boron sulfide, gallium sulfide, tin sulfide (SnS, SnS2), aluminum sulfide, and zinc sulfide; phosphoric acid compounds such as sodium phosphate and lithium phosphate; halides of alkali metals other than lithium such as sodium iodide, sodium fluoride, sodium chloride, and sodium bromide; metal halides such as aluminum halides, silicon halides, germanium halides, arsenic halides, selenium halides, tin halides, antimony halides, tellurium halides, and bismuth halides; halogenated phosphorus oxides such as phosphorus oxychloride (POCl3) and phosphorus oxybromide (POBr3); and the like.

[0162] From the viewpoint of more easily obtaining a solid electrolyte with high ion conductivity, as raw materials, lithium sulfide, phosphorus trisulfide (P2S3), phosphorus pentasulfide (P2S5) and other phosphorus sulfides are preferred among the above, and when using raw materials containing halogen atoms, halogen monomers (halogen molecules) such as fluorine (F2), chlorine (Cl2), bromine (Br2), iodine (I2), lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide are preferred. As a combination of raw materials, for example, a combination of lithium sulfide, phosphorus pentasulfide and lithium halide, a combination of lithium sulfide, phosphorus pentasulfide and halogen monomers can be preferably exemplified, lithium bromide and lithium iodide are preferred as lithium halides, and bromine and iodine are preferred as halogen monomers.

[0163] The lithium sulfide used in the present embodiment is preferably in the form of particles.

[0164] The median diameter of lithium sulfide particles (D 50 ) is preferably 10 μm to 2000 μm, more preferably 30 μm to 1500 μm, and even more preferably 50 μm to 1000 μm. In this specification, the median diameter (D 50) is the particle size when the particle size reaches 50% of the total when the particle size distribution cumulative curve is drawn, and the volume distribution is, for example, the median diameter that can be measured using a laser diffraction / scattering particle size distribution measuring device. In addition, among the substances exemplified as the above-mentioned raw materials, it is preferred that the solid raw material has a median diameter of the same degree as that of the lithium sulfide particles, that is, the median diameter is preferably within the same range as that of the lithium sulfide particles.

[0165] <Solution of Intermediate (1)>

[0166] The intermediate (1) used in this embodiment includes at least one of the above-mentioned raw material content, the complex described below, and the solid electrolyte described below, and the following schemes (i) to (iii) can be representatively exemplified. In order to control the particle size of the solid electrolyte, the solution of the intermediate (1) containing a solvent in which the raw material content can be dissolved is preferably a solution of (i) to (iii), more preferably a solution of (i) or (ii), and further preferably a solution of (ii).

[0167] (i) The above-mentioned raw material-containing substance (including the above-mentioned raw material) is contained as a main component.

[0168] (ii) Contains a complex as a main component.

[0169] (iii) Contains a solid electrolyte as a main component.

[0170] For example, the above (ii) means that it may contain raw material content or solid electrolyte, but contains complex as the main component. In this specification, "main component" means a component of 50% by mass or more of the components other than the solvent, and "containing as the main component" means containing as the main component in a dissolved state.

[0171] The intermediate (1) contains the atomic species contained in the above-mentioned raw material-containing substance.

[0172] <Solid Electrolyte>

[0173] The solid electrolyte in the present embodiment includes, in addition to the solid electrolyte produced in the present embodiment, a solid electrolyte that is an intermediate produced in the production process of the production method of the present embodiment and further reacts with other compounds.

[0174] The solid electrolyte manufactured in the present embodiment is obtained by drying using a spray drying device, so it is solid, preferably granular. The solid electrolyte obtained by the manufacturing method of the present embodiment includes both a crystalline solid electrolyte and an amorphous solid electrolyte having a crystal structure. In this specification, "crystalline solid electrolyte" refers to a solid electrolyte in which a peak derived from a solid electrolyte is observed in an X-ray diffraction pattern in an X-ray diffraction measurement, and is a material that is independent of the peak of the raw material derived from the solid electrolyte. That is, the crystalline solid electrolyte includes a crystal structure derived from a solid electrolyte, and may be a part of it derived from the crystal structure of the solid electrolyte, or it may be a whole of it derived from the crystal structure of the solid electrolyte. In addition, as long as the crystalline solid electrolyte has such an X-ray diffraction pattern as described above, an amorphous solid electrolyte may also be included in a part of it. Therefore, the crystalline solid electrolyte includes a so-called glass ceramic obtained by heating an amorphous solid electrolyte to a temperature above the crystallization temperature.

[0175] In this specification, “amorphous solid electrolyte” means that the X-ray diffraction pattern is a halo pattern in which substantially no peaks other than peaks derived from the material are observed in X-ray diffraction measurement, regardless of the presence or absence of peaks derived from the raw materials of the solid electrolyte.

[0176] In addition, the content of lithium atoms, phosphorus atoms and sulfur atoms in the solid electrolyte can be determined based on the measurement of the inductively coupled plasma (ICP) emission spectrometer described in the embodiment, and the content of organic groups can be determined by focusing on the characteristic functional groups of the organic groups and appropriately combining Fourier transform infrared spectrophotometer (FT-IR), solid nuclear magnetic resonance (NMR) spectroscopy, gas chromatography, gas chromatography-mass spectrometer (GC-Mass), etc.

[0177] (Amorphous solid electrolyte)

[0178] The amorphous solid electrolyte obtained by the manufacturing method of this embodiment preferably contains lithium atoms, sulfur atoms, phosphorus atoms and further contains halogen atoms as needed. Representative amorphous solid electrolytes include Li2S-P2S5; Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr and other solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide; and solid electrolytes containing other atoms such as oxygen atoms and silicon atoms, such as Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI and the like. From the perspective of obtaining higher ion conductivity, amorphous solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr, are preferred.

[0179] The types of atoms constituting the amorphous solid electrolyte can be confirmed by, for example, an ICP emission spectrometer.

[0180] (Crystalline Solid Electrolyte)

[0181] The crystalline solid electrolyte obtained by the manufacturing method of this embodiment can be a so-called glass ceramic obtained by heating an amorphous solid electrolyte to a temperature above the crystallization temperature, and its crystal structure can be exemplified by Li3PS4 crystal structure, Li4P2S6 crystal structure, Li7PS6 crystal structure, Li7P3S 11 A crystal structure, a crystal structure having peaks near 2θ=20.2° and 23.6° (for example, Japanese Patent Application Laid-Open No. 2013-16423), and the like.

[0182] As a crystalline solid electrolyte containing a halogen atom, a crystalline solid electrolyte having the following crystal structure can be preferably exemplified: an argyrodite-type crystal structure having the structural skeleton of the above-mentioned Li7PS6 and in which a part of P is substituted with Si.

[0183] As the composition formula of the argyrodite type crystal structure, for example, the composition formula Li 7-x P 1-y Si y S6 and Li 7+x P 1- y Si yThe crystal structure represented by S6 (where x ranges from -0.6 to 0.6 and y ranges from 0.1 to 0.6). The thiogermanate-type crystal structure represented by this composition formula is cubic or orthorhombic, preferably cubic. In X-ray diffraction measurements using CuKα radiation, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0184] As a composition formula of the thiogermanate-type crystal structure, the composition formula Li 7-x-2y PS 6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5) can also be cited. The thiogermanate-type crystal structure represented by this composition formula is preferably cubic. In X-ray diffraction measurements using CuKα radiation, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0185] In addition, as a composition formula of the thiogermanate-type crystal structure, the composition formula Li 7-x PS 6-x Ha x (where Ha is Cl or Br, and x is preferably from 0.2 to 1.8) can also be cited. The thiogermanate-type crystal structure represented by this composition formula is preferably cubic. In X-ray diffraction measurements using CuKα radiation, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0186] In addition, these peak positions can fluctuate within a range of ±0.5°.

[0187] The Li 4-x Ge 1-x P x S4 type of sulfide crystalline lithium superionic conductor region II (thio-LISICON Region II) type crystal structure (refer to Kanno et al., Journal of The Electrochemical Society, 148(7) A742 - 746(2001)), and the Li 4-x Ge 1-x P xS4 type thio-LISICON Region II type crystal structure (see Solid State Ionics, 177 (2006), 2721-2725). From the perspective of obtaining higher ionic conductivity, the crystal structure of the crystalline solid electrolyte obtained by the solid electrolyte manufacturing method of this embodiment is preferably a thio-LISICON Region II type crystal structure among the above. Here, "thio-LISICON Region II type crystal structure" means Li 4-x Ge 1- x P x S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure, and Li 4-x Ge 1- x P x Any crystal structure similar to the S4 type thio-LISICON Region II type.

[0188] The crystalline solid electrolyte obtained by the manufacturing method of this embodiment may be a crystalline solid electrolyte containing the above-mentioned sulfide crystalline lithium superion conductor region type II crystal structure, or may be a crystalline solid electrolyte containing the sulfide crystalline lithium superion conductor region type II crystal structure as a main crystal. From the viewpoint of obtaining higher ionic conductivity, it is preferred to contain the sulfide crystalline lithium superion conductor region type II crystal structure as a main crystal. In this specification, "containing as a main crystal" means that the proportion of the crystal structure as the object in the crystal structure is 80% or more, preferably 90% or more, and more preferably 95% or more. In addition, from the viewpoint of obtaining higher ionic conductivity, the crystalline solid electrolyte obtained by the manufacturing method of this embodiment preferably does not contain crystalline Li3PS4 (β-Li3PS4).

[0189] In the X-ray diffraction measurement using CuKα rays, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ=17.5°, 18.3°, 26.1°, 27.3°, and 30.0°; the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ=16.9°, 27.1°, and 32.5°; the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ=15.3°, 25.2°, 29.6°, and 31.0°; and the diffraction peaks of the Li7P3S 11 The diffraction peaks of the crystal structure appear near 2θ=17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°, for example.4-x Ge 1-x P x The diffraction peaks of the S4-type sulfide crystalline lithium superion conductor region II (thio-LISICONRegion II) crystal structure appear near 2θ=20.1°, 23.9°, and 29.5°, which are similar to Li 4-x Ge 1-x P x The diffraction peaks of the S4 type thio-LISICON Region II-type crystal structure appear near 2θ=20.2° and 23.6°, for example. These peak positions may fluctuate within a range of ±0.5°.

[0190] In the solid electrolyte produced in the present embodiment, as a crystalline solid electrolyte, the contents of lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms are the same as those of the above-mentioned amorphous solid electrolyte.

[0191] (Properties of solid electrolyte)

[0192] The solid electrolyte obtained by the production method of the present embodiment is in the shape of particles.

[0193] The median diameter of the solid electrolyte particles (D 50 ) is preferably less than 9.0 μm. As a result, it is easy to form a contact interface between the electrode active material and the solid electrolyte, and the paths of ion conduction and electron conduction become good. From the same point of view, it is more preferably 8.9 μm or less, more preferably 8.0 μm or less, more preferably 7.0 μm or less, and particularly preferably 6.5 μm or less. The median diameter (D 50 ) can be adjusted by changing the spray pressure of the spray drying device. The lower limit is not particularly limited, and from the perspective of the performance and productivity of the spray drying device, for example, preferably 0.01 μm or more, 0.03 μm or more, 0.05 μm or more, 0.1 μm or more, more preferably 0.8 μm or more, further preferably 1.0 μm or more, and even more preferably 1.5 μm or more.

[0194] Therefore, in the manufacturing method of the present embodiment, the operation of crushing (micronizing) the solid electrolyte obtained by the manufacturing method of the present embodiment may not be performed. By not crushing, it is not necessary to use a crusher, so in order to improve productivity, it is preferred not to further crush the solid electrolyte obtained by the manufacturing method of the present embodiment.

[0195] Similarly, the particle size (D 10) is preferably 0.05 μm to 10.0 μm, more preferably 0.50 μm to 6.0 μm, and even more preferably 1.0 μm to 4.0 μm.

[0196] In addition, the particle size (D 90 ) is preferably from 0.10 μm to 20.0 μm, more preferably from 1.0 μm to 15.0 μm, and even more preferably from 3.0 μm to 10.0 μm.

[0197] The particle size distribution of the solid electrolyte particles is given by (D 90 -D 10 ) / D 50 It is indicated that if it is 3.00 or less, it can be said that the particle size distribution is narrow, so it is preferred. From the same viewpoint, it is more preferably 2.50 or less, further preferably 2.00 or less, further preferably 1.50 or less, and particularly preferably 1.25 or less. The lower limit is not particularly limited, but is 0.01 or more from the performance and productivity of the spray drying device.

[0198] The median diameter of the solid electrolyte can be measured, for example, by the measurement method described in the examples. Figure 2 Judging from the shape of the particle size distribution of the solid electrolyte produced as shown, it can be read that the particle size distribution of the solid electrolyte (1) is narrower than that of the solid electrolyte (C1).

[0199] The specific surface area of ​​the solid electrolyte particles is preferably 15 m 2 / g or more. If the solid electrolyte has a high specific surface area, it is easy to pack tightly when making a battery, so it is easy to obtain excellent battery performance. From the same point of view, the specific surface area of ​​the solid electrolyte is more preferably 16m 2 / g or more, more preferably 17m 2 / g or more, more preferably 18m 2 The upper limit is not particularly limited, but is 50 m / g based on the performance and productivity of the spray drying device. 2 / g or less.

[0200] In this specification, the specific surface area of ​​the solid electrolyte is a measured value measured by the method described in Examples.

[0201] The crystallite size of the solid electrolyte of the present embodiment is preferably 30 nm or more. From the viewpoint of improving ionic conductivity, it is preferably 33 nm or more, more preferably 35 nm or more, further preferably 40 nm or more, further preferably 70 nm or more, and more preferably 80 nm or more. The upper limit is not particularly limited, but from the perspective of productivity, it is preferably 300 nm or less, more preferably 250 nm or less, further preferably 200 nm or less, further preferably 150 nm or less, and more preferably 130 nm or less.

[0202] The ionic conductivity of the solid electrolyte of the present embodiment obtained by the manufacturing method of the present embodiment is extremely high due to the controlled particle size, and can generally be 0.01 mS / cm or more. It is more preferably 1.00 mS / cm or more, further preferably 2.00 mS / cm or more, further preferably 2.50 mS / cm or more, more preferably 3.00 mS / cm or more, and particularly preferably 3.50 mS / cm or more. The upper limit is not particularly limited.

[0203] In this specification, the ion conductivity of the solid electrolyte is a measured value measured by the method described in the Examples.

[0204] (use)

[0205] The solid electrolyte obtained by the manufacturing method of this embodiment has a controlled particle size and can be used for battery manufacturing, so it can effectively demonstrate excellent battery performance. In addition, since the ion conductivity is high and the battery performance is excellent, it is preferably used in batteries.

[0206] The solid electrolyte obtained by the production method of this embodiment can be used for the positive electrode layer, the negative electrode layer, or the electrolyte layer. In addition, these layers can be produced by a known method.

[0207] In addition, the battery preferably uses a current collector in addition to the positive electrode layer, the electrolyte layer and the negative electrode layer, and the current collector can use a known current collector. For example, a layer obtained by coating a substance that reacts with the solid electrolyte such as Au, Pt, Al, Ti or Cu can be used.

[0208] <Solvent>

[0209] The solvent used in the manufacturing method of the present embodiment can be widely used in the manufacture of solid electrolytes. According to its properties and uses, non-polar solvents, complexing agents and raw material-containing solubilizing solvents can be cited. The solvent preferably contains at least one selected from complexing agents and raw material-containing solubilizing solvents. By making the solvent contain a raw material-containing solubilizing solvent, a solution of the intermediate (1) can be easily obtained, the particle size of the manufactured solid electrolyte can be controlled, and productivity can be improved, so it is preferred. By making the solvent contain a complexing agent, a solid electrolyte with high ionic conductivity can be manufactured as described later, so it is preferred.

[0210] It is preferred that the solvent further contains a nonpolar solvent described below because the amount of the complexing agent or the solvent that dissolves the raw material content used can be reduced as necessary.

[0211] When two or more solvents are combined, preferred combinations include a combination comprising a complexing agent and a solvent that can solubilize the raw material contents, a combination comprising a nonpolar solvent and a solvent that can solubilize the raw material contents, and a combination comprising a nonpolar solvent, a complexing agent, and a solvent that can solubilize the raw material contents.

[0212] Furthermore, a nonpolar solvent, a complexing agent, and a solvent other than the solvent in which the raw material-containing substance can be solubilized may be contained.

[0213] The details of non-polar solvent, complexing agent and raw material containing material solubilizing solvent will be described later. In this specification, "non-polar solvent" is used with the same meaning as that commonly used. However, complexing agent and raw material containing material solubilizing solvent cannot be clearly distinguished. For example, there is a raw material containing material solubilizing solvent that forms a complex with the raw material containing material, and there is also a complexing agent that dissolves the raw material containing material. In addition, when using multiple compounds as solvents, a compound with a relatively strong ability to form a complex with the raw material containing material is used as a complexing agent, and a compound with a relatively weak ability to form a complex with the raw material containing material but dissolves the raw material containing material is used as a raw material containing material solubilizing solvent. Therefore, whether it becomes a complexing agent or a raw material containing material solubilizing solvent depends on the ability to form a complex with the raw material containing material relative to the combined compound. Of course, depending on whether the solvent is a single compound or a combination of compounds, it sometimes also has the effects of both complexing agents and raw material containing material solubilizing solvents.

[0214] In order to obtain a narrow particle size distribution and a median diameter (D 50 ) is a small solid electrolyte, the amount of solvent used is preferably 0.1 g to 50.0 g, more preferably 1.0 g to 30.0 g, and even more preferably 5.0 g to 25.0 g, relative to 1 g of the total mass of the raw material contents.

[0215] Hereinafter, the solvent in which the raw material-containing substance is solubilized, the nonpolar solvent and the complexing agent will be described.

[0216] (Solvents in which raw material contents can be dissolved)

[0217] The raw material-containing substance-soluble solvent used in the manufacturing method of the present embodiment is a solvent capable of forming a solution of the intermediate (1). The raw material-containing substance-soluble solvent is a solvent that dissolves the raw material contents. The raw material-containing substance-soluble solvent preferably dissolves the complex and / or the solid electrolyte in addition to the raw material contents. That is, the raw material-containing substance-soluble solvent is preferably a solvent that forms a solution of the intermediate (1) in which the complex and / or the solid electrolyte are dissolved in addition to the raw material contents. The raw material-containing substance-soluble solvent is not particularly limited as long as it shows the above-mentioned properties. From the viewpoint of the solubility of the raw material contents, the complex and the solid electrolyte, it is preferably an alcohol solvent, and more preferably an alcohol solvent.

[0218] Specific examples of alcohol solvents include: aliphatic primary alcohols and aliphatic secondary alcohols such as methanol, ethanol, isopropanol, butanol, and 2-ethylhexanol; polyols such as ethylene glycol, propylene glycol, butanediol, and hexanediol; alicyclic alcohols such as cyclopentanol, cyclohexanol, and cyclopentylmethanol; aromatic alcohols such as butylphenol, benzyl alcohol, phenylethyl alcohol, naphthol, and diphenylmethanol; alkoxy alcohols such as methoxyethanol, propoxyethanol, and butoxyethanol; and the like.

[0219] As the alcohol solvent, among the various solvents described above, aliphatic alcohols are preferred, primary aliphatic alcohols are more preferred, methanol and ethanol are further preferred, and ethanol is particularly preferred.

[0220] In order to obtain a narrow particle size distribution and a median diameter (D 50 ) is a small solid electrolyte, the amount of the solvent for solubilizing the raw material contents used is preferably 0.1 g to 50.0 g, more preferably 0.5 g to 30.0 g, further preferably 1.0 g to 25.0 g, and even more preferably 3.0 g to 20.0 g, relative to 1 g of the total mass of the raw material contents.

[0221] (Complexing agent)

[0222] The complexing agent used in the manufacturing method of this embodiment is a compound that forms a complex with the raw material content, for example, a compound that can form a complex with lithium sulfide, phosphorus pentasulfide, which are preferably used as raw material content, and Li3PS4 obtained when using them, and raw material content containing halogen atoms.

[0223] In particular, when the raw material contains halogen atoms, the formation of complexes obtained by the action of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms is promoted, and it is easy to make the structure containing lithium such as PS4 structure or the aggregate via the complexing agent, the raw material containing lithium such as lithium halide or the aggregate via the complexing agent more widespread. Thus, a solid electrolyte with more dispersed and fixed halogen atoms can be obtained, so it is easy to obtain high ionic conductivity.

[0224] As the complexing agent, any complexing agent having the above-mentioned properties can be used without particular limitation, and in particular, preferably, compounds containing atoms having high affinity with lithium atoms, such as nitrogen atoms, oxygen atoms, chlorine atoms and other heteroatoms can be exemplified, and more preferably, compounds containing groups containing these heteroatoms can be exemplified. This is because these heteroatoms and groups containing these heteroatoms can coordinate (bond) with lithium.

[0225] It is believed that the heteroatoms present in the molecules of the complexing agent have a high affinity for lithium atoms and have the property of easily bonding with the raw material content and the like to form a complex (hereinafter also referred to as a "complex"). Therefore, it is believed that by mixing the raw material content and the complexing agent to form a complex, it is easy to uniformly maintain the dispersion state of the raw material content, especially the dispersion state of the halogen atoms, so that a solid electrolyte with high ion conductivity can be obtained.

[0226] In addition, by forming a complex between the raw material content and the solid electrolyte (especially Li3PS4), it is difficult for the raw material content and the solvent that can dissolve the raw material content to come into direct contact with the raw material content, thereby suppressing the reaction between the solvent that can dissolve the raw material content and the raw material content, etc., which is preferred.

[0227] Whether the complexing agent can form a complex with the raw material content or the like can be directly confirmed by, for example, infrared absorption spectrum measured by FT-IR analysis (diffuse reflectance method).

[0228] In the production method of the present embodiment, as the complexing agent, a compound containing an oxygen atom as a heteroatom is preferred.

[0229] As the compound containing an oxygen atom, a compound having one or more functional groups selected from an ether group and an ester group as a group containing an oxygen atom is preferred, and a compound having an ether group is particularly preferred. That is, as the complexing agent containing an oxygen atom, an ether compound is particularly preferred.

[0230] Examples of the ether compound include ether compounds such as aliphatic ether, alicyclic ether, heterocyclic ether and aromatic ether, and these ether compounds may be used alone or in combination of two or more.

[0231] More specifically, the aliphatic ethers include monoethers such as dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, and tert-butyl methyl ether; diethers such as dimethoxymethane, dimethoxyethane, diethoxymethane, and diethoxyethane; polyethers having three or more ether groups such as diethylene glycol dimethyl ether (diglyme) and triethylene glycol dimethyl ether (triglyme); and ethers containing hydroxyl groups such as diethylene glycol and triethylene glycol.

[0232] The carbon number of the aliphatic ether is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less.

[0233] The carbon number of the aliphatic hydrocarbon group in the aliphatic ether is preferably 1 or more, and the upper limit is preferably 6 or less, more preferably 4 or less, and further preferably 3 or less.

[0234] Examples of the alicyclic ether include ethylene oxide, propylene oxide, tetrahydrofuran (THF), tetrahydropyran, dimethoxytetrahydrofuran, cyclopentyl methyl ether, dioxane, dioxolane, and the like. Examples of the heterocyclic ether include furan, benzofuran, benzopyran, dioxine, dioxin, morpholine, methoxyindole, and hydroxymethyldimethoxypyridine.

[0235] As the alicyclic ether, tetrahydrofuran is preferred.

[0236] The carbon number of the alicyclic ether or heterocyclic ether is preferably 3 or more, more preferably 4 or more, and the upper limit is preferably 16 or less, more preferably 14 or less.

[0237] Examples of the aromatic ether include methyl phenyl ether (anisole), ethyl phenyl ether, dibenzyl ether, diphenyl ether, benzyl phenyl ether and naphthyl ether.

[0238] The number of carbon atoms in the aromatic ether is preferably 7 or more, more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 12 or less.

[0239] The ether compound used in the present embodiment may be an ether compound substituted with a substituent such as an alkyl group, an alkenyl group, an alkoxy group, a hydroxyl group, a cyano group, or a halogen atom.

[0240] Among the above ether compounds, from the viewpoint of obtaining higher ion conductivity, aliphatic ethers or alicyclic ethers are preferred, dimethoxyethane or tetrahydrofuran is more preferred, and tetrahydrofuran is further preferred.

[0241] Examples of the ester compound include ester compounds such as aliphatic esters, alicyclic esters, heterocyclic esters and aromatic esters, and these ester compounds may be used alone or in combination of two or more.

[0242] More specifically, the aliphatic esters include formic acid esters such as methyl formate, ethyl formate and triethyl formate; acetates such as methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate and isobutyl acetate; propionic acid esters such as methyl propionate, ethyl propionate, propyl propionate and butyl propionate; oxalic acid esters such as dimethyl oxalate and diethyl oxalate; malonic acid esters such as dimethyl malonate and diethyl malonate; and succinic acid esters such as dimethyl succinate and diethyl succinate.

[0243] The carbon number of the aliphatic ester is preferably 2 or more, more preferably 3 or more, and further preferably 4 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and further preferably 7 or less. In addition, the carbon number of the aliphatic hydrocarbon group in the aliphatic ester is preferably 1 or more, more preferably 2 or more, and the upper limit is preferably 6 or less, more preferably 4 or less, and further preferably 3 or less.

[0244] Examples of the alicyclic esters include methyl cyclohexanecarboxylate, ethyl cyclohexanecarboxylate, dimethyl cyclohexanedicarboxylate, dibutyl cyclohexenedicarboxylate, and dibutyl cyclohexenedicarboxylate. Examples of the heterocyclic esters include methyl pyridinecarboxylate, ethyl pyridinecarboxylate, propyl pyridinecarboxylate, methyl pyrimidinecarboxylate, ethyl pyrimidinecarboxylate, or lactones such as acetone, propiolactone, butyrolactone, and valerolactone.

[0245] The carbon number of the alicyclic ester or heterocyclic ester is preferably 3 or more, more preferably 4 or more, and the upper limit is preferably 16 or less, more preferably 14 or less.

[0246] Examples of the aromatic ester include benzoic acid esters such as methyl benzoate, ethyl benzoate, propyl benzoate, and butyl benzoate; phthalic acid esters such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, butyl benzyl phthalate, and dicyclohexyl phthalate; and trimellitic acid esters such as trimethyl trimellitic acid, triethyl trimellitic acid, tripropyl trimellitic acid, tributyl trimellitic acid, and trioctyl trimellitic acid.

[0247] The number of carbon atoms in the aromatic ester is preferably 8 or more, more preferably 9 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 12 or less.

[0248] The ester compound used in the present embodiment may be an ester compound substituted with a substituent such as an alkyl group, an alkenyl group, an alkoxy group, a hydroxyl group, a cyano group, or a halogen atom.

[0249] From the viewpoint of obtaining higher ion conductivity, among the above ester compounds, aliphatic esters are preferred, acetates are more preferred, and ethyl acetate is particularly preferred.

[0250] Furthermore, as the hetero atom, a nitrogen atom is preferred, and as the group containing a nitrogen atom, an amino group is preferred, that is, the complexing agent preferably contains a compound having an amino group.

[0251] The amine compound having an amino group in the molecule can promote the formation of the electrolyte precursor and is therefore not particularly limited, but the complexing agent preferably contains a compound having at least two tertiary amino groups in the molecule.

[0252] By having such a structure, a lithium-containing structure such as Li3PS4 containing a PS4 structure can be bonded to a lithium-containing raw material such as a lithium halide via at least two nitrogen atoms in the molecule, so that the halogen atoms are more dispersed and fixed in the electrolyte precursor, resulting in a solid electrolyte with high ionic conductivity.

[0253] Examples of such amine compounds include amine compounds such as aliphatic amines, alicyclic amines, heterocyclic amines and aromatic amines, and these amine compounds may be used alone or in combination of two or more.

[0254] More specifically, the aliphatic amines may be preferably and representatively exemplified: aliphatic primary diamines such as ethylenediamine, diaminopropane, and diaminobutane; aliphatic secondary diamines such as N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N'-dimethyldiaminopropane, and N,N'-diethyldiaminopropane; aliphatic tertiary diamines such as N,N,N',N'-tetramethyldiaminomethane, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, N,N,N',N'-tetramethyldiaminopropane, N,N,N',N'-tetraethyldiaminopropane, N,N,N',N'-tetramethyldiaminobutane, N,N,N',N'-tetramethyldiaminopentane, and N,N,N',N'-tetramethyldiaminohexane; and the like. Here, in the examples of this specification, for example, if diaminobutane is used, unless otherwise specified, all isomers such as linear and branched isomers of butane are included in addition to isomers related to the position of the amino group such as 1,2-diaminobutane, 1,3-diaminobutane, and 1,4-diaminobutane.

[0255] The carbon number of the aliphatic amine is preferably 2 or more, more preferably 4 or more, and further preferably 6 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and further preferably 7 or less. In addition, the carbon number of the hydrocarbon group of the aliphatic hydrocarbon group in the aliphatic amine is preferably 2 or more, and the upper limit is preferably 6 or less, more preferably 4 or less, and further preferably 3 or less.

[0256] The alicyclic amines may be preferably and representatively exemplified as primary alicyclic diamines such as cyclopropylene diamine and cyclohexyl diamine; secondary alicyclic diamines such as bisaminomethyl cyclohexane; tertiary alicyclic diamines such as N,N,N',N'-tetramethyl-cyclohexyl diamine and bis(ethylmethylamino)cyclohexane; and the like. Furthermore, the heterocyclic amines may be preferably and representatively exemplified as primary heterocyclic diamines such as isophorone diamine; secondary heterocyclic diamines such as piperazine and dipiperidyl propane; tertiary heterocyclic diamines such as N,N-dimethylpiperazine and bismethylpiperidyl propane; and the like.

[0257] The carbon number of the alicyclic amine or heterocyclic amine is preferably 3 or more, more preferably 4 or more, and the upper limit is preferably 16 or less, more preferably 14 or less.

[0258] In addition, as the aromatic amine, representative and preferred examples include: aromatic primary diamines such as phenylenediamine, toluenediamine, and naphthalenediamine; aromatic secondary diamines such as N-methylphenylenediamine, N,N'-dimethylphenylenediamine, N,N'-dimethylnaphthalenediamine, and N-naphthylethylenediamine; aromatic tertiary diamines such as N,N-dimethylphenylenediamine, N,N,N',N'-tetramethylphenylenediamine, N,N,N',N'-tetramethyldiaminodiphenylmethane, and N,N,N',N'-tetramethylnaphthalenediamine; and other aromatic diamines.

[0259] The number of carbon atoms in the aromatic amine is preferably 6 or more, more preferably 7 or more, and even more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and even more preferably 12 or less.

[0260] The amine compound used in the present embodiment may be an amine compound substituted with a substituent such as an alkyl group, an alkenyl group, an alkoxy group, a hydroxyl group, a cyano group, or a halogen atom.

[0261] In addition, although diamines are illustrated as specific examples, the amine compounds that can be used in the present embodiment are obviously not limited to diamines. For example, trimethylamine, triethylamine, ethyldimethylamine, aliphatic monoamines corresponding to various diamines such as the above-mentioned aliphatic diamines; piperidine compounds such as piperidine, methylpiperidine, and tetramethylpiperidine; pyridine compounds such as pyridine and methylpyridine; morpholine compounds such as morpholine, methylmorpholine, and thiomorpholine; imidazole compounds such as imidazole and methylimidazole; and cyclopentadiene compounds corresponding to the above-mentioned alicyclic diamines. In addition, alicyclic monoamines such as monoamine; heterocyclic monoamines corresponding to the above-mentioned heterocyclic diamines; aromatic monoamines corresponding to the above-mentioned aromatic diamines, etc., can also be used. For example, polyamines having three or more amino groups such as diethylenetriamine, N,N',N"-trimethyldiethylenetriamine, N,N,N',N",N"-pentamethyldiethylenetriamine, triethylenetetramine, N,N'-bis[(dimethylamino)ethyl]-N,N'-dimethylethylenediamine, hexamethylenetetramine, tetraethylenepentamine, etc. can also be used.

[0262] Among the above, from the viewpoint of obtaining higher ion conductivity, a tertiary amine having a tertiary amino group as an amino group is preferred, a tertiary diamine having two tertiary amino groups is more preferred, a tertiary diamine having two tertiary amino groups at both terminals is further preferred, and an aliphatic tertiary diamine having tertiary amino groups at both terminals is further preferred. Among the above amine compounds, as the aliphatic tertiary diamine having tertiary amino groups at both terminals, tetramethylethylenediamine, tetraethylethylenediamine, tetramethyldiaminopropane, and tetraethyldiaminopropane are preferred. In consideration of availability, tetramethylethylenediamine and tetramethyldiaminopropane are preferred.

[0263] In order to obtain a narrow particle size distribution and a median diameter (D 50 ) is a small solid electrolyte, the amount of the complexing agent used is preferably 0.1g to 50.0g, more preferably 0.5g to 30.0g, further preferably 1.0g to 20.0g, and even more preferably 3.0g to 10.0g, relative to 1g of the total mass of the raw material contents.

[0264] (Non-polar solvent)

[0265] The non-polar solvent used in the manufacturing method of this embodiment is preferably a solvent that is difficult to dissolve the raw material content and the solid electrolyte. Specifically, it is preferably not a solvent containing heteroatoms as preferably exemplified as the complexing agent and the raw material content solubilizing solvent, but a hydrocarbon solvent that does not contain heteroatoms. By using a non-polar solvent, the use amount of the complexing agent and the raw material content solubilizing solvent can be reduced, so it is preferred. As a non-polar solvent, examples include: aliphatic hydrocarbon solvents such as pentane, hexane, 2-ethylhexane, heptane, octane, decane, undecane, dodecane, and tridecane; alicyclic hydrocarbon solvents such as cyclohexane, methylcyclohexane, and ethylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, mesitylene, ethylbenzene, and tert-butylbenzene, etc., and can be appropriately selected from these.

[0266] Among these solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents are preferred, and aromatic hydrocarbon solvents are more preferred. More specifically, 2-ethylhexane, heptane, octane, cyclohexane, methylcyclohexane, benzene, toluene, xylene, or mesitylene are preferred, methylcyclohexane, benzene, toluene, or xylene are more preferred, and toluene is further preferred.

[0267] They can be used individually or in combination.

[0268] In order to obtain a narrow particle size distribution and a median diameter (D 50) is a small solid electrolyte, the amount of the non-polar solvent used is preferably 0.1 g to 50.0 g, more preferably 0.5 g to 30.0 g, further preferably 1.0 g to 20.0 g, and even more preferably 3.0 g to 10.0 g, relative to 1 g of the total mass of the raw material contents.

[0269] (heating)

[0270] The method for manufacturing the solid electrolyte of the present embodiment preferably further includes heating. It is possible to preferably heat after mixing the solid electrolyte, and more preferably heat after spraying the solution of the intermediate (1). When the solution of the intermediate (1) is sprayed using a spray drying device, it is also preferably heated as described above, but depending on the heating temperature, sometimes the removal of the complexing agent in the complex is insufficient, or the crystals contained in the solid electrolyte are not fully grown. In such a case, it is preferably further included to heat. That is, it is preferably included: heating the complex to obtain the amorphous solid electrolyte described later; and obtaining the crystalline solid electrolyte described later by heating the complex or the amorphous solid electrolyte.

[0271] By heating the complex, the complexing agent and solvent in the complex are removed, and an amorphous solid electrolyte and / or a crystalline solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms can be obtained.

[0272] Furthermore, heating the crystalline solid electrolyte to increase the crystallite size can also improve the ion conductivity, which is preferred.

[0273] Here, the fact that the complexing agent in the complex is removed can be confirmed by the fact that the complexing agent constitutes a eutectic of the precursor as shown in the results of X-ray diffraction pattern, gas chromatography analysis, etc., and in addition, it can be confirmed by the fact that the solid electrolyte obtained by removing the complexing agent by heating the complex is the same as the X-ray diffraction pattern of the solid electrolyte obtained by the conventional method without using the complexing agent.

[0274] In the manufacturing method of the present embodiment, the solid electrolyte is obtained by heating the complex to remove the complexing agent in the complex, and the less complexing agent in the solid electrolyte is preferred, but the complexing agent may also be included to a degree that does not damage the performance of the solid electrolyte. The content of the complexing agent in the solid electrolyte is usually 10% by mass or less, preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 1% by mass or less. The less the content, the more preferred, so the lower limit is not particularly limited.

[0275] In the production method of the present embodiment, the crystalline solid electrolyte may be obtained by heating the complex, or the complex may be heated to obtain an amorphous solid electrolyte, and then the amorphous solid electrolyte may be heated to obtain the crystalline solid electrolyte.

[0276] In the method for manufacturing a solid electrolyte of the present embodiment, whether to obtain an amorphous solid electrolyte or a crystalline solid electrolyte, and further whether to obtain a crystalline solid electrolyte after obtaining an amorphous solid electrolyte, or to obtain a crystalline solid electrolyte directly from a complex, can be appropriately selected according to the desired conditions and can be adjusted by heating temperature, heating time, etc.

[0277] Regarding the heating temperature of the complex, for example, in the case of obtaining an amorphous solid electrolyte, the heating temperature can be determined according to the structure of the crystalline solid electrolyte obtained by heating the amorphous solid electrolyte (or complex). Specifically, a differential thermal analysis (DTA) is performed on the amorphous solid electrolyte (or complex) under a temperature increase condition of 10°C / minute using a differential thermal analysis device (DTA device), and the temperature of the peak top of the exothermic peak observed on the lowest temperature side is preferably set to a range of 5°C or less, more preferably set to a range of 10°C or less, and further preferably set to a range of 20°C or less. There is no particular restriction on the lower limit, and it can be set to a temperature of about -40°C or more of the peak top of the exothermic peak observed on the lowest temperature side. By setting such a temperature range, an amorphous solid electrolyte can be obtained more efficiently and reliably.

[0278] The heating temperature for obtaining an amorphous solid electrolyte cannot be generally specified because it varies depending on the structure of the obtained crystalline solid electrolyte, but is generally preferably below 250°C, more preferably below 220°C, and further preferably below 200°C. There is no particular restriction on the lower limit, but it is preferably above 90°C, more preferably above 100°C, and further preferably above 110°C.

[0279] In addition, it is preferred to carry out heating under reduced pressure. From the perspective of the device, it is preferably above 0.1 Pa, more preferably above 1.0 Pa, and further preferably above 5.0 Pa. From the perspective of obtaining a solid electrolyte with high ion conductivity, it is preferably below 100.0 Pa, more preferably below 50.0 Pa, and further preferably below 20.0 Pa.

[0280] In addition, when heating an amorphous solid electrolyte or directly obtaining a crystalline solid electrolyte from a complex, the heating temperature can be determined according to the structure of the crystalline solid electrolyte, preferably higher than the above-mentioned heating temperature for obtaining an amorphous solid electrolyte. Specifically, a differential thermal analysis device (DTA device) is used to perform differential thermal analysis (DTA) on the amorphous solid electrolyte (or complex) under a temperature increase condition of 10°C / minute, and the temperature of the peak top of the exothermic peak observed on the lowest temperature side is used as the starting point, preferably set to 5°C or more, more preferably set to 10°C or more, and further preferably set to 20°C or more. There is no particular limit as the upper limit, and it can be set to about 40°C or less. By setting it to such a temperature range, a crystalline solid electrolyte can be obtained more efficiently and reliably. The heating temperature for obtaining a crystalline solid electrolyte cannot be generally specified because it varies depending on the structure of the obtained crystalline solid electrolyte, but is generally preferably above 200°C, more preferably above 300°C, and further preferably above 350°C. There is no particular upper limit, but it is preferably below 600°C, more preferably below 500°C, and further preferably below 450°C.

[0281] The heating time is not particularly limited as long as the desired amorphous solid electrolyte and crystalline solid electrolyte can be obtained, for example, preferably more than 1 minute, more preferably more than 10 minutes, more preferably more than 30 minutes, and more preferably more than 1 hour. In addition, the upper limit of the heating time is not particularly limited, preferably less than 24 hours, more preferably less than 20 hours, more preferably less than 15 hours, and more preferably less than 10 hours.

[0282] In addition, the heating is preferably carried out in an inert gas atmosphere (e.g., a nitrogen atmosphere, an argon atmosphere) or in a reduced pressure atmosphere (particularly in a vacuum). This is because it is possible to prevent degradation (e.g., oxidation) of the crystalline solid electrolyte. The method of heating is not particularly limited, and for example, methods using a heating plate, a vacuum heating device, an argon atmosphere furnace, a firing furnace, etc. can be cited. In addition, in industry, a horizontal dryer, a horizontal vibrating fluidized dryer, etc. having a heating unit and a feeding mechanism can also be used, and the selection can be made according to the amount of heating treatment.

[0283] (crushed)

[0284] The method for producing a solid electrolyte of the present embodiment may further include pulverizing the solid electrolyte, but since the solvent is removed from the intermediate (1) using a spray drying device under specific conditions, the particle size of the produced solid electrolyte is controlled. Therefore, in order to improve productivity, it is preferred that after spraying the solution of the intermediate (1), no further pulverization of the solid electrolyte is performed.

[0285] When pulverizing, the above-mentioned pulverizer can be used.

[0286] 〔Solid electrolyte〕

[0287] The solid electrolyte of this embodiment is a solid electrolyte in which the median diameter (D 50 ) is 1.0 μm or more and less than 9.0 μm, based on the median diameter (D 50 ) and the particle size of 10% of the cumulative volume (D 10 ) and the particle size at which 90% of the cumulative volume is located (D 90 ) particle size distribution ((D 90 -D 10 ) / D 50 ) is less than 2.50. As described above, the method for manufacturing the solid electrolyte of the present embodiment is not particularly limited, and for example, the solid electrolyte can be easily manufactured by the method for manufacturing the solid electrolyte of the present embodiment described above, and the solid electrolyte manufactured has the above-specified median diameter and particle size distribution.

[0288] The median diameter (D 50 ) is 1.0 μm or more and less than 9.0 μm. From the viewpoint of easily forming the contact interface between the electrode active material and the solid electrolyte and making the path of ion conduction and electron conduction good, the upper limit is preferably 8.9 μm or less, more preferably 8.0 μm or less, further preferably 7.0 μm or less, and further preferably 6.5 μm or less. As the lower limit, as long as it is 1.0 μm or more, there is no particular restriction. For example, in the case of manufacturing by the manufacturing method of the present embodiment, from the viewpoint of the performance and productivity of the spray drying device, it is preferably 1.5 μm or more, more preferably 2.0 μm or more, and further preferably 3.0 μm or more.

[0289] The particle size (D 10 ) is preferably 0.05 μm to 10.0 μm, more preferably 0.50 μm to 6.0 μm, and even more preferably 1.0 μm to 4.0 μm.

[0290] In addition, the particle size (D 90 ) is preferably from 0.10 μm to 20.0 μm, more preferably from 1.0 μm to 15.0 μm, and even more preferably from 3.0 μm to 10.0 μm.

[0291] The particle size distribution (D 90 -D 10 ) / D 50It is 2.50 or less, and from the viewpoint of easily forming the contact interface between the electrode active material and the solid electrolyte and making the path of ion conduction and electron conduction good, the upper limit is preferably 2.25 or less, more preferably 2.00 or less, further preferably 1.50 or less, and further preferably 1.25 or less. In addition, as the lower limit, it is not particularly limited, and from the viewpoint of the performance and productivity of the spray drying device, it is set to 0.01 or more, preferably 0.1 or more.

[0292] The specific surface area of ​​the solid electrolyte of this embodiment is preferably 15 cm 2 / g or more. If the solid electrolyte has a high specific surface area, it is easy to be densely packed when the battery is made, so it is easy to obtain excellent battery performance. Regarding the more preferred specific surface area, it is the same as the range described as the specific surface area that the solid electrolyte obtained by the manufacturing method of the present embodiment described above can have.

[0293] Regarding the solid electrolyte of the present embodiment, properties other than the above-mentioned median diameter and particle size distribution, such as the ability to become an amorphous solid electrolyte and a crystalline solid electrolyte, and the atoms constituting the solid electrolyte and their ratios, are the same as those described for the solid electrolyte obtained by the method for manufacturing the solid electrolyte of the present embodiment mentioned above.

[0294] When the solid electrolyte of the present embodiment is a crystalline solid electrolyte, it preferably has a sulfide crystalline lithium superion conductor region II type crystal structure or an argyrodite type crystal structure as a crystal structure, and more preferably has an argyrodite type crystal structure. These crystal structures are the same as those described as the solid electrolyte obtained by the method for producing the solid electrolyte of the present embodiment described above.

[0295] Example

[0296] Next, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples at all.

[0297] (1) Measurement method

[0298] (1-1) Median diameter (D 50 ) and the 10% and 90% particle sizes of the cumulative distribution (D 10 )(D 90 )

[0299] The volume-based median diameter is measured using a laser diffraction / scattering particle size distribution measuring device ("Partica LA-950V2 Model LA-950W2", manufactured by Horiba, Ltd.). A mixture of dehydrated toluene (special grade, manufactured by Wako Pure Chemical Industries, Ltd.) and tert-butyl alcohol (special grade, manufactured by Wako Pure Chemical Industries, Ltd.) at a weight ratio of 93.8:6.2 is used as a dispersion medium. 50 ml of the dispersion medium is injected into the flow cell of the device and circulated, and then the measurement object is put in for ultrasonic treatment, and then the particle size distribution is measured. In addition, the input amount of the measurement object is adjusted so that in the measurement screen specified in the device, the red light transmittance (R) corresponding to the particle concentration converges to 70 to 90%, and the blue light transmittance (B) converges to 80 to 90%. In addition, for the calculation conditions, 2.16 is used as the value of the refractive index of the measurement object, and 1.49 is used as the value of the refractive index of the dispersion medium. In the distribution form setting, the number of repetitions was fixed at 15 times to perform particle size calculation and calculate the median diameter (D 50 In addition, the 10% particle size (D 10 ) and 90% particle size (D 90 ), and calculate the particle size distribution ((D 90 -D 10 ) / D 50 ).

[0300] (1-2) Ionic conductivity measurement

[0301] In this example, the measurement of ion conductivity was performed as follows.

[0302] The solid electrolyte is formed into a 10 mm diameter (cross-sectional area S: 0.785 cm 2 ), round particles with a height (L) of 0.1 to 0.3 cm are used to make a sample. The top and bottom of the sample are taken as electrode terminals, and the AC impedance method is used for measurement at 25°C (frequency range: 1 MHz to 100 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. Near the right end of the arc observed in the high-frequency side area, the real part Z'(Ω) at the point where -Z"(Ω) is the smallest is taken as the bulk resistance R(Ω) of the electrolyte, and the ionic conductivity σ(S / cm) is calculated according to the following formula.

[0303] R=ρ(L / S)

[0304] σ=1 / ρ

[0305] (1-3) Measurement of specific surface area

[0306] In this example, the specific surface area was measured using a gas adsorption measurement device by the BET method based on krypton (Kr) adsorption.

[0307] (Example 1)

[0308] In an anaerobic glove box, 122.20 g of Li2S, 155.61 g of P2S5, 72.94 g of LiCl, and 59.33 g of LiBr were weighed as raw material contents into a separable flask equipped with a stirrer and a condenser, 1820 g of toluene as a non-polar solvent and 1864 g of tetrahydrofuran (THF) as a complexing agent were added (toluene and THF were added to form a slurry containing 10% by mass of the raw material contents), and the mixture was stirred at room temperature for 166 hours to obtain a slurry-like intermediate (1-1).

[0309] Then, 3313 g of ethanol as a solvent for dissolving the raw material content was further added to the separable flask containing the intermediate (1-1) (by adding ethanol, the mass of the raw material content used in the solution was 5 mass%), and stirring was continued to prepare a solution (intermediate (1-2)). After confirming that it has become a solution, the solution of the intermediate (1-2) was dried using a spray drying device (manufactured by Okawara Chemical Machinery Co., Ltd., device name: CNL-3) with a spray pressure of 0.30 MPa, a drying inlet temperature of 200°C, and a feeding rate of 20 g / min to produce a solid electrolyte (1).

[0310] Table 1 shows the median diameter of the solid electrolyte (1).

[0311] From the XRD pattern, it was confirmed that the solid electrolyte (1) was a solid electrolyte including an argyrodite crystal structure.

[0312] The solid electrolyte (1) was heated at 430°C for 8 hours in a nitrogen atmosphere. The ion conductivity of the obtained solid electrolyte was measured by the above-mentioned ion conductivity measurement method. In addition, the median diameter and the 10% particle size of the cumulative distribution (D 10 ) and 90% particle size (D 90 The results are shown in Table 1. Table 1 also shows the median diameter and the 10% particle size (D 10 ) and 90% particle size (D 90 ) Calculated particle size distribution ((D 90 -D 10 ) / D 50 ).

[0313] (Example 2)

[0314] Intermediate (1-3), intermediate (1-4) and solid electrolyte (2) were produced in the same manner as in Example 1 except that the spray pressure was changed to 0.05 MPa.

[0315] The XRD pattern confirmed that the solid electrolyte (2) was a solid electrolyte having an argyrodite crystal structure. The median diameter of the solid electrolyte (2) is shown in Table 1.

[0316] The solid electrolyte (2) was heated at 430°C for 8 hours in a nitrogen atmosphere. The obtained solid electrolyte was used to measure the ion conductivity by the above-mentioned ion conductivity measurement method. In addition, the median diameter and the 10% particle size of the cumulative distribution (D 10 ) and 90% particle size (D 90 The results are shown in Table 1. Table 1 also shows the median diameter and the 10% particle size (D 10 ) and 90% particle size (D 90 ) Calculated particle size distribution ((D 90 -D 10 ) / D 50 ).

[0317] (Comparative Example 1)

[0318] The solid component of the intermediate (1-2) obtained in Example 1 was separated by decantation. Toluene was added to the separated solid component and then the solid component was separated by decantation again. This washing operation was performed three times. Then, the obtained solid component was transferred to a flask and vacuum dried at 200° C. for 3 hours to recover the solid component (solid electrolyte (C1)).

[0319] Table 1 shows the median diameter of the solid electrolyte (C1).

[0320] The solid electrolyte (C1) was heated at 430°C for 8 hours in a nitrogen atmosphere. The XRD pattern confirmed that it was a solid electrolyte containing a argyrodite crystal structure. The obtained solid electrolyte was used to measure the ion conductivity by the above-mentioned ion conductivity measurement method. In addition, for the solid electrolyte obtained by heating, the median diameter and the 10% particle size of the cumulative distribution (D 10 ) and 90% particle size (D 90 The results are shown in Table 1. Table 1 also shows the median diameter and the 10% particle size (D 10 ) and 90% particle size (D 90 ) Calculated particle size distribution ((D 90 -D 10 ) / D 50 ).

[0321] (Comparative Example 2)

[0322] In an anaerobic glove box, 122.20 g of Li2S, 155.61 g of P2S5, 72.94 g of LiCl, and 59.33 g of LiBr were weighed as raw materials into a separable flask equipped with a stirrer and a condenser, and 8232 g of pyridine was added under ice cooling while stirring. After returning to room temperature and 20 hours, it was heated to 80°C and reacted for 5 hours to obtain a slurry containing the intermediate (C2).

[0323] The solid electrolyte (C2) is obtained by spraying the slurry containing the intermediate (C2) using a spray drying apparatus under the same conditions as in Example 1, except that the solution of the intermediate (1-2) is replaced by a slurry containing the intermediate (C2) and the spray pressure is set to 0.6 MPa.

[0324] The XRD pattern confirmed that the solid electrolyte (C2) was a solid electrolyte having an argyrodite crystal structure. The median diameter of the solid electrolyte (2) is shown in Table 1.

[0325] The solid electrolyte (C2) was heated at 430° C. for 8 hours in a nitrogen atmosphere. In addition, the median diameter and the 10% cumulative distribution particle size (D 10 ) and 90% particle size (D 90 ), and specific surface area. The obtained solid electrolyte was used to measure the ion conductivity by the above-mentioned ion conductivity measurement method. The results are recorded in Table 1. Table 1 also shows the median diameter and the 10% particle size (D 10 ) and 90% particle size (D 90 ) Calculated particle size distribution ((D 90 -D 10 ) / D 50 ).

[0326] The median diameters and ionic conductivities of the obtained solid electrolyte (1), solid electrolyte (2), solid electrolyte (C1) and solid electrolyte (C2) are shown in the following table.

[0327] [Table 1]

[0328] Table 1

[0329]

[0330] The median diameter (D 50 ) is small, the particle size distribution is small, and therefore narrow, and the ionic conductivity is 4.9 and 5.4 mS / cm, which is excellent. In addition, it can be considered that the specific surface area is large and is 19 cm2 / g, it is easy to pack densely when manufacturing a battery, so it is easy to obtain excellent battery performance. Furthermore, as described in Examples 1 and 2, it is known that the productivity is also excellent.

[0331] In contrast, it can be seen that the solid electrolyte (C1) produced in Comparative Example 1 is a small droplet, and unlike the case where a spray drying device is used to instantly dry the solvent, when heated and vacuum dried in a flask, the dried particles are granulated, and the median diameter (D 50 ) becomes larger.

[0332] The particle size distributions of the solid electrolyte (1), the solid electrolyte (2) and the solid electrolyte (C1) are shown in Figure 2 .Depend on Figure 2 It can be seen that the particle size distribution of solid electrolyte (C1) is multimodal and not narrow compared with solid electrolyte (1) and solid electrolyte (2). This can also be understood from the following: 90 -D 10 ) / D 50 ), and 3.32 in the solid electrolyte (C1), which is larger than 1.17 and 0.87 of the solid electrolytes (1) and (2). In addition, as shown in Table 1, the ionic conductivity is also poor. The decrease in ionic conductivity is believed to be caused by the fact that the drying in the flask is different from the drying using a spray drying device, and the distribution of the elements forming the solid electrolyte is disturbed in the uniformity in the solid electrolyte, and the content of the argyrodite crystal structure is reduced. The main reason for the decrease in the content of the argyrodite crystal structure is that the halogen element is not uniformly distributed in the solid electrolyte, and a large amount of impurities as a solid solution containing the halogen element are generated.

[0333] For the solid electrolyte (C2) prepared in Comparative Example 2, the slurry was sprayed using a spray drying device instead of spraying the intermediate solution, and the median diameter (D 50 ) becomes larger as shown in Table 1. This is considered to be because when the slurry is sprayed, the particle size of the sprayed droplets cannot be controlled, and the particle size of the solid component in the slurry is not controlled, so the median diameter (D 50 ) becomes larger. Solid electrolytes (1) and (2) have excellent ion conductivity compared to solid electrolyte (C2), and the reason is considered to be as follows: by making a solution as in Examples 1 and 2, the distribution of atoms forming the solid electrolyte becomes uniform in the solid electrolyte. In other words, it is considered that if the slurry is sprayed, the distribution of atoms in the solid electrolyte becomes uneven, so even if the same raw materials as in the example are used at the same ratio, the ion conductivity of the same degree as in the example cannot be obtained.

[0334] Industrial Applicability

[0335] According to the method for producing a solid electrolyte of this embodiment, it is possible to easily produce a solid electrolyte having a narrow particle size distribution and a median diameter (D 50 ) small solid electrolyte.

[0336] The solid electrolyte obtained by the production method of this embodiment or the solid electrolyte of this embodiment is suitable for lithium ion batteries, particularly lithium ion batteries used in information-related equipment or communication equipment such as personal computers, video cameras and mobile phones.

Claims

1. A method for producing a solid electrolyte, characterized in that: include: Mixing a raw material containing lithium atoms, phosphorus atoms and sulfur atoms with a solvent to obtain a solution of an intermediate (1); as well as The solution of the intermediate (1) is sprayed using a spray dryer at a spray pressure of 0.01 MPa or more.

2. The method for producing a solid electrolyte according to claim 1, wherein: The spray pressure is 0.05 MPa or more.

3. A method for producing a solid electrolyte, characterized in that: include: Mixing a raw material containing lithium atoms, phosphorus atoms and sulfur atoms with a solvent to obtain a solution of an intermediate (1); as well as The solution of the intermediate (1) is sprayed using a spray drying apparatus.

4. The method for producing a solid electrolyte according to any one of claims 1 to 3, wherein: The median diameter (D 50 ) is less than 9.0μm.

5. The method for producing a solid electrolyte according to any one of claims 1 to 4, wherein: The temperature of the intermediate (1) at the spray outlet of the spray drying device is 350°C or less.

6. The method for producing a solid electrolyte according to any one of claims 1 to 5, wherein: No further pulverization of the solid electrolyte was performed.

7. The method for producing a solid electrolyte according to any one of claims 1 to 6, wherein: The raw material-containing substance further contains a halogen atom.

8. The method for producing a solid electrolyte according to any one of claims 1 to 7, wherein: The solvent includes at least one selected from a complexing agent and a solvent in which the raw material-containing substance can be dissolved.

9. The method for producing a solid electrolyte according to claim 8, wherein: The solvent includes a solvent in which the raw material-containing substances can be dissolved.

10. The method for producing a solid electrolyte according to claim 8 or 9, characterized in that: The solvent contains a complexing agent.

11. The method for producing a solid electrolyte according to any one of claims 8 to 10, wherein: The solvent in which the raw material-containing substance can be dissolved includes an alcohol solvent.

12. The method for producing a solid electrolyte according to any one of claims 8 to 11, wherein: The solvent further comprises a non-polar solvent.

13. The method for producing a solid electrolyte according to any one of claims 8 to 12, wherein: After the raw material-containing substance and the solvent containing the complexing agent are mixed, a solvent containing a solvent in which the raw material-containing substance can be dissolved is further added and mixed.

14. A solid electrolyte, characterized in that: Median diameter (D 50 ) is 1.0 μm or more and less than 9.0 μm, based on the median diameter (D 50 ) and the particle size of 10% of the cumulative volume (D 10 ) and the particle size at which 90% of the cumulative volume is located (D 90 ) particle size distribution ((D 90 -D 10 ) / D 50 ) is less than 2.

50.

15. The solid electrolyte according to claim 14, characterized in that The specific surface area is 15cm 2 / g or above.

16. The solid electrolyte according to claim 14 or 15, characterized in that It has a argyrodite-type crystal structure.

Citation Information

Patent Citations

  • Solid sulfide electrolyte material, solid-state lithium battery, and method for manufacturing solid sulfide electrolyte material

    JP2013016423A

  • Producing method of particles

    JP2017018872A

  • Method for producing solid electrolyte

    JP2019169459A